Method for producing aqueous composition

Aqueous and emulsified compositions with a cationic-anionic-nonionic polymer complex provide improved stability and durability, addressing stability and moisture resistance issues in cosmetic and fiber treatments.

CN119255787APending Publication Date: 2025-01-03KAO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380041680.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-23
Filing Date
2023-05-26
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing cosmetic and fiber treatment compositions containing polyion complexes face issues with stability and durability, particularly in high humidity conditions, leading to loss of texture and moisture resistance after a single shampooing or washing.

Method used

A method for producing an aqueous and emulsified composition comprising a cationic polymer, an anionic polymer, a nonionic polymer, and an acid, involving specific mixing steps to form a polyion complex with a cross-linked structure, enhancing stability and sustainability of the treatment effect.

Benefits of technology

The compositions exhibit improved texture, tangling suppression, and moisture resistance, maintaining effectiveness even under high humidity conditions, with enhanced stability and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143465930000111
    Figure BDA0005143465930000111
  • Figure BDA0005143465930000381
    Figure BDA0005143465930000381
  • Figure BDA0005143465930000501
    Figure BDA0005143465930000501
Patent Text Reader

Abstract

This method for producing an aqueous composition comprises the following steps 1-3 in this order: step 1: a step for preparing a mixture 1 containing (B) an anionic polymer, (C) a nonionic polymer, and water, and step 2: a step for mixing the mixture 1 with (D) an acid or an aqueous solution thereof to prepare a mixture 2 containing (B) an anionic polymer, (C) a nonionic polymer, (D) an acid, and water, step 3: a step for mixing the mixture 2 with (A) a cationic polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an aqueous composition and an emulsified composition. Background Art

[0002] Cosmetic compositions containing cationic polymers and anionic polymers are known. For example, Japanese Patent Laid-Open No. 53-139734 (Patent Document 1) describes a composition for treating keratinous substances, characterized in that at least one anionic polymer and at least one cationic polymer are contained in a solvent medium, and by using the composition, the anionic polymer can be fixed to keratinous substances including hair, skin or nails. In addition, as a reason for obtaining the above-mentioned effect, it is presumed that it is related to the complex formed by the interaction between the anionic polymer and the cationic polymer.

[0003] As compositions containing complexes formed of cationic polymers and anionic polymers (hereinafter also referred to as "polyion complexes"), there are known forms of water-in-oil type or oil-in-water type emulsion compositions. Generally speaking, the problem with emulsion compositions is to improve stability over time, and stable emulsion compositions or methods for producing stable emulsion compositions have also been studied.

[0004] For example, Japanese Patent Application Laid-Open No. 11-116445 (Patent Document 2) discloses that a hair treatment composition is produced by a step of emulsifying oil and water using a surfactant, a step of dissolving a powdered cationic polymer and a powdered anionic polymer in water, and a step of mixing these. This makes it possible to easily produce a hair treatment composition in which a polymer supplied in a powdered state is prepared in a stable emulsified state.

[0005] Japanese Patent Publication No. 2020-536857 (Patent Document 3) discloses a cosmetic composition such as a skin care product, which comprises: a specified polymerization product obtained by reacting a system comprising an anionic polymer, an amphoteric polymer and water; an arbitrary cationic polymer; an arbitrary active ingredient; an arbitrary additive; and an arbitrary medium that can be tolerated in cosmetics, which can allow the active ingredient to remain on the hair in a sufficiently effective amount after rinsing the hair, thereby making the hair easy to comb, smooth, soft, and moisturized, and providing nutrition to the hair, and on the other hand, making it easy to rinse other ingredients in the skin care product other than the active ingredient. In addition, as a method for manufacturing the composition, the following method is disclosed, which includes: mixing a system comprising the above-mentioned anionic polymer, the above-mentioned amphoteric polymer and water to react to obtain the above-mentioned polymerization product; and mixing the above-mentioned polymerization product, an arbitrary cationic polymer, an arbitrary active ingredient, an arbitrary additive, and an arbitrary medium that can be tolerated in cosmetics to obtain the above-mentioned composition.

[0006] Japanese Patent Publication No. 2021-31468 (Patent Document 4) discloses a cosmetic composition for keratin fibers, which comprises at least one polyion complex, at least one texture agent such as a hydrophilic thickener, and water, and the cosmetic composition for keratin fibers provides smoothness, softness, and improved texture such as less stickiness to keratin fibers such as hair, wherein the at least one polyion complex comprises: at least one ionic polymer selected from a group consisting of cationic polymers, anionic polymers, amphoteric polymers, and mixtures thereof, and a specified crosslinking agent. In addition, the following method is described in the examples: an aqueous solution of a cationic polymer is mixed with an acidic compound to prepare a gel solution of a polyion complex, a nonionic polymer is added thereto for homogenization, and a uniform composition in the form of an emulsion is obtained. Summary of the invention

[0007] The present invention relates to the following contents.

[0008] [1] A method for producing an aqueous composition, wherein:

[0009] The aqueous composition contains (A) a cationic polymer, (B) an anionic polymer, (C) a nonionic polymer, (D) an acid, and water.

[0010] The above-mentioned manufacturing method comprises the following steps 1 to 3 in sequence.

[0011] Step 1: a step of preparing a mixture 1 comprising (B) an anionic polymer, (C) a nonionic polymer and water,

[0012] Step 2: a step of mixing the mixture 1 with (D) an acid or an aqueous solution thereof to prepare a mixture 2 comprising (B) an anionic polymer, (C) a nonionic polymer, (D) an acid and water,

[0013] Step 3: A step of mixing the mixture 2 and the (A) cationic polymer.

[0014] [2] A method for producing an emulsified composition, comprising:

[0015] The emulsified composition contains (A) a cationic polymer, (B) an anionic polymer, (C) a nonionic polymer, (D) an acid, an oily component, and water.

[0016] The above-mentioned production method sequentially comprises the following steps 1 to 3, and any one of the steps 4-1 or 4-2.

[0017] Step 1: a step of preparing a mixture 1 comprising (B) an anionic polymer, (C) a nonionic polymer and water,

[0018] Step 2: a step of mixing the mixture 1 with (D) an acid or an aqueous solution thereof to prepare a mixture 2 comprising (B) an anionic polymer, (C) a nonionic polymer, (D) an acid and water,

[0019] Step 3: a step of mixing the mixture 2 with the (A) cationic polymer to prepare a mixture 3 comprising the (A) cationic polymer, the (B) anionic polymer, the (C) nonionic polymer, the (D) acid and water,

[0020] Step 4-1: A step of mixing an aqueous phase containing water and an oil phase containing an oily component to prepare an emulsion, and then mixing the emulsion with the mixture 3.

[0021] Step 4-2: A step of mixing the mixture 3 with an aqueous phase containing water and then mixing with an oil phase containing an oil component to emulsify the mixture. DETAILED DESCRIPTION

[0022] As described above, compositions containing polyion complexes and methods for producing the same have been studied in the past. However, there is still room for improvement in terms of improving the performance of compositions containing polyion complexes when used as cosmetic compositions or fiber treatment compositions for headdress products.

[0023] For example, in a hair conditioner which is one type of hair cosmetic composition, it is required that the texture of the treated hair is improved, tangles are suppressed, the treated hair does not split even under high humidity conditions, and has excellent moisture resistance, etc. Furthermore, the treatment effect on the hair may be lost after one shampooing, and it is desired to improve the durability of the treatment effect (wash resistance).

[0024] As a method for improving the touch of hair when applied to hair or after treatment, a method of blending a cationic surfactant, a higher alcohol, etc. in a hair conditioner is generally known. However, an emulsified composition in which these components are blended in a composition containing a polyion complex has a problem of low stability.

[0025] The present invention relates to a method for producing an aqueous composition and an emulsified composition. The aqueous composition and the emulsified composition contain a polyion complex and have high stability. The aqueous composition and the emulsified composition can improve the texture improvement effect of the treated object and the sustainability of the effect, as well as the moisture resistance. In particular, when used for treating hair or fibers for hair accessories, the aqueous composition and the emulsified composition can improve the knot suppression effect of the hair or fibers for hair accessories and the sustainability of the effect, and can suppress the split ends of the treated hair or fibers for hair accessories under high humidity conditions.

[0026] The present inventors have found that the above-mentioned problems can be solved by producing an aqueous composition containing a cationic polymer, an anionic polymer, a nonionic polymer, an acid and water through a specific process and producing an emulsified composition using the aqueous composition.

[0027] According to the present invention, there is provided a method for producing an aqueous composition and an emulsified composition, wherein the aqueous composition and the emulsified composition contain a polyion complex and have high stability, and can improve the texture-enhancing effect of the treated object and the sustainability of the effect, as well as moisture resistance. In particular, when used for treating hair or fibers for headdress products, the aqueous composition and the emulsified composition can improve the tangle-inhibiting effect of the hair or fibers for headdress products and the sustainability of the effect, and can inhibit the split ends of the treated hair or fibers for headdress products under high humidity conditions.

[0028] [Method for producing aqueous composition and emulsified composition]

[0029] The present invention relates to a method for producing an aqueous composition, wherein the aqueous composition contains (A) a cationic polymer, (B) an anionic polymer, (C) a nonionic polymer, (D) an acid, and water.

[0030] The above-mentioned manufacturing method comprises the following steps 1 to 3 in sequence.

[0031] Step 1: a step of preparing a mixture 1 comprising (B) an anionic polymer, (C) a nonionic polymer and water,

[0032] Step 2: a step of mixing the mixture 1 with (D) an acid or an aqueous solution thereof to prepare a mixture 2 comprising (B) an anionic polymer, (C) a nonionic polymer, (D) an acid and water,

[0033] Step 3: A step of mixing the mixture 2 and the (A) cationic polymer.

[0034] The present invention also relates to a method for producing an emulsion composition, wherein the emulsion composition contains (A) a cationic polymer, (B) an anionic polymer, (C) a nonionic polymer, (D) an acid, an oily component, and water.

[0035] The above-mentioned production method sequentially comprises the following steps 1 to 3, and any one of the steps 4-1 or 4-2.

[0036] Step 1: a step of preparing a mixture 1 comprising (B) an anionic polymer, (C) a nonionic polymer and water,

[0037] Step 2: a step of mixing the mixture 1 with (D) an acid or an aqueous solution thereof to prepare a mixture 2 comprising (B) an anionic polymer, (C) a nonionic polymer, (D) an acid and water,

[0038] Step 3: a step of mixing the mixture 2 with the (A) cationic polymer to prepare a mixture 3 comprising the (A) cationic polymer, the (B) anionic polymer, the (C) nonionic polymer, the (D) acid and water,

[0039] Step 4-1: A step of mixing an aqueous phase containing water and an oil phase containing an oily component to prepare an emulsion, and then mixing the emulsion with the mixture 3.

[0040] Step 4-2: A step of mixing the mixture 3 with an aqueous phase containing water and then mixing with an oil phase containing an oil component to emulsify the mixture.

[0041] <Definition>

[0042] Hereinafter, the aqueous composition and the emulsified composition are collectively referred to as a "composition", and the production method is collectively referred to as a "production method of the present invention".

[0043] In the present specification, the “aqueous phase” means a component constituting the aqueous phase in the production process of the emulsified composition, and the “oil phase” means a component constituting the oil phase in the production process of the emulsified composition.

[0044] According to the manufacturing method of the present invention, it is possible to provide a method for manufacturing an aqueous composition and an emulsified composition, which contain a polyion complex, have high stability, can improve the texture improvement effect of the treated object and the sustainability of the effect, and moisture resistance, and in particular, when used for treating hair or fibers for hair accessories, can improve the tangling suppression effect of hair or fibers for hair accessories and the sustainability of the effect, and can suppress the split ends of the treated hair or fibers for hair accessories under high humidity conditions. Hereinafter, steps 4-1 and 4-2 are sometimes collectively referred to as "step 4".

[0045] The reason why the production method of the present invention achieves the above-mentioned effects is not certain, but the reason is considered to be as follows.

[0046] The composition produced by the present invention comprises a polyion complex formed by component (A) and component (B). It is believed that in the polyion complex, a cross-linked structure is formed between component (A) and component (B) by ionic interaction, and thus, the coating obtained using the composition of the present invention exhibits a higher elastic modulus.

[0047] Further, the composition manufactured by the present invention contains a nonionic polymer as component (C). It is believed that the rigid cross-linked structure of the polyion complex formed by component (A) and component (B) strengthens the coating obtained by using the composition through the composite of the long-chain and soft non-cross-linked structure of component (C). In addition, it is believed that since hydrogen bonding can be carried out between component (B)-component (C), component (C) is retained in the above-mentioned cross-linked structure by component (B), thereby forming a further high-strength network structure in the coating. Thus, it is believed that if the above-mentioned composition is used, the texture and moisture resistance of the object to be treated can be improved even by a single treatment, and even if it is cleaned afterwards, the treatment effect will not be lost, and the continuity of the effect can be obtained.

[0048] In the manufacturing method of the present invention, first, in step 1, a mixture 1 comprising (B) anionic polymer, (C) nonionic polymer and water is prepared. Then, the mixture 1 is mixed with (D) acid or its aqueous solution (step 2), and finally mixed with (A) cationic polymer (step 3). By first performing step 1, component (B) and component (C) are hydrogen bonded, and component (C) is easily immobilized in the cross-linked structure of the polyion complex through component (B). Therefore, it is believed that: even if washing is performed after the film is formed, component (C) will not be rinsed away and is likely to remain in the film, and the sustainability of the treatment effect is improved.

[0049] In addition, the mixture 1 is mixed with (D) an acid or an aqueous solution thereof in step 2, and (A) a cationic polymer is sequentially mixed in step 3, thereby forming the above-mentioned network gel containing a polyion complex with high stability. Therefore, it is considered that: in the production of the emulsified composition, even if the oil phase is prepared in step 4 to form an emulsion, the above-mentioned network gel does not cause aggregation, separation, etc., but is dispersed in a good state, so that the stability of the emulsified composition is improved.

[0050] Furthermore, it is believed that when the aqueous composition and the emulsified composition are used to treat hair or fibers for hair accessories, the well-dispersed mesh gel is uniformly attached to the hair, thereby improving the tangle-inhibiting effect and the sustainability of the tangle-inhibiting effect on the hair or fibers for hair accessories, and inhibiting the split ends of the treated hair or fibers for hair accessories under high humidity conditions.

[0051] The composition produced by the present invention is preferably a cosmetic composition for keratin substances such as skin, hair, eyelashes, eyebrows, nails, or a fiber treatment composition for headwear products, more preferably a cosmetic composition for skin or hair, and a fiber treatment composition for headwear products, further preferably a cosmetic composition for skin or hair, and even more preferably a hair cosmetic composition.

[0052] Among cosmetic compositions, examples of product forms of skin cosmetic compositions include body washes, facial cleansers, bath preparations, deodorant preparations, makeup products, sunscreens, primers, emulsions, beauty serums, and face creams.

[0053] In addition, examples of product forms of the hair cosmetic composition include shampoo, hair rinse, hair conditioner, hair treatment (including leave-in), styling agent, hair dye, hair perm, etc. Among these, hair conditioner, hair treatment, or styling agent is preferred from the viewpoint of effectiveness of the effect of the present invention.

[0054] As the fiber for headdress products, it can be any type of fiber derived from nature or synthetic fiber, but it is preferably derived from nature. Fibers derived from nature refer to fibers collected from natural animals and plants, or fibers artificially manufactured using collagen, casein, soybeans, peanuts, corn, silk scraps, silk protein, etc. as raw materials and used in headdress products. Among these, preferably, fibers artificially manufactured using collagen, casein, soybeans, peanuts, corn, silk scraps, silk protein, etc. as raw materials, more preferably regenerated collagen fibers using collagen as raw materials, regenerated silk fibers using silk protein as raw materials, and other regenerated protein fibers, and more preferably regenerated collagen fibers.

[0055] Regenerated collagen fibers can be produced using known techniques. The composition of regenerated collagen fibers does not need to be 100% collagen, and may also contain natural polymers, synthetic polymers, additives, etc. for improving quality. Furthermore, regenerated collagen fibers may also be post-processed.

[0056] As the form of the regenerated collagen fiber, filaments are preferably used. The filaments are generally taken out from a reel or a boxed state. In addition, in the production process of the regenerated collagen fiber, the filaments obtained from the drying process can also be directly used.

[0057] As synthetic fibers, fibers containing synthetic resins as main components can be cited. From the viewpoint of ease of manufacturing of synthetic fibers and the viewpoint of obtaining a texture close to that of hair, the synthetic resin is preferably a thermoplastic resin, and more preferably one or more selected from polyester resins, polyamide resins, polyimide resins, polyamide-imide resins, vinyl chloride resins, polycarbonate resins, polyphenylene sulfide resins, and modified acrylic resins (copolymers of acrylonitrile and vinyl chloride). The "main component" mentioned here refers to a component whose content in the synthetic fiber is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, further more preferably 80% by mass or more, further more preferably 90% by mass or more, and is 100% by mass or less.

[0058] In addition to the synthetic resin, the synthetic fiber may further contain various components such as flame retardants, flame retardant aids, light or heat stabilizers, fluorescent agents, antioxidants, antistatic agents, ultraviolet absorbers, etc. within a range that does not impair the effects of the present invention.

[0059] In addition, from the viewpoint of stability and the viewpoint of improving the feeling during use, the emulsified composition produced by the present invention is preferably an oil-in-water emulsified composition.

[0060] Hereinafter, each component prepared in the aqueous composition and the emulsified composition will be described.

[0061] (Component (A): cationic polymer)

[0062] The (A) cationic polymer is a polymer that can form a polyion complex through interaction with the (B) anionic polymer.

[0063] The cationic polymer as component (A) is preferably a polymer having a cationic group and having a positive charge as a total charge. In component (A), in addition to the cationic group, an anionic group, a nonionic group, or an amphoteric group such as a betaine group may be contained within a range that does not impair the effects of the present invention.

[0064] In the present specification, the cationic group is a cationic group or a group that can become a cationic group by ionization, and specific examples thereof include a primary amino group, a secondary amino group, a tertiary amino group, and a quaternary ammonium group.

[0065] The anionic group is an anionic group or a group that can be ionized to become an anionic group. Specifically, one or more of acidic groups such as carboxyl, sulfonic acid, and phosphoric acid can be cited, preferably one or more of carboxyl and sulfonic acid, more preferably carboxyl. At least a portion of the anionic group can also be neutralized to become a salt state.

[0066] Component (A) is preferably a cationic polymer having a viscosity of 1,000 mPa·s or more in a 1% by mass aqueous solution at 30°C. It is believed that by using the component (A) having a viscosity of 1,000 mPa·s or more, the lubricity of the obtained coating is improved, so the texture of the treated object is further improved, and when used for treating hair or fibers for hair ornaments, the effect of inhibiting tangling of the fibers for hair ornaments is improved. In addition, it is believed that since the polyion complex containing the component (A) has high stability, even when an oily component is added to form an emulsified composition, the structure of the polyion complex is not easily destroyed, thereby improving stability.

[0067] From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the anti-tangling effect of hair or fibers for hair ornament products and the sustainability of the effect when used for treating hair or fibers for hair ornament products, improving moisture resistance, and improving the stability of the composition, the viscosity of a 1 mass % aqueous solution of component (A) at 30° C. is more preferably 1,300 mPa·s or more, further preferably 1,500 mPa·s or more, further preferably 1,700 mPa·s or more, and further more preferably 1,800 mPa·s or more. The upper limit of the viscosity is not particularly limited, but from the viewpoint of the ease of forming a polyion complex and the handleability, it is preferably 100,000 mPa·s or less, more preferably 80,000 mPa·s or less, further preferably 50,000 mPa·s or less, further more preferably 30,000 mPa·s or less, and further more preferably 25,000 mPa·s or less. Furthermore, the viscosity of a 1 mass % aqueous solution of component (A) at 30° C. is preferably 1,000 mPa·s or more, more preferably 1,000 mPa·s or more and 100,000 mPa·s or less, further preferably 1,300 mPa·s or more and 80,000 mPa·s or less, further more preferably 1,500 mPa·s or more and 50,000 mPa·s or less, further more preferably 1,700 mPa·s or more and 30,000 mPa·s or less, further more preferably 1,800 mPa·s or more and 25,000 mPa·s or less.

[0068] The cationic charge density of component (A) is preferably 0.1 mmol / g or more, more preferably 0.2 mmol / g or more, further preferably 0.3 mmol / g or more, and further preferably 0.5 mmol / g or more, from the viewpoint of facilitating the formation of a polyion complex by interaction with component (B), improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, improving moisture resistance, and improving the stability of the composition. In addition, from the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, improving the moisture resistance, and improving the stability of the composition, it is preferably 20 mmol / g or less, more preferably 15 mmol / g or less, further preferably 12 mmol / g or less, further more preferably 10 mmol / g or less, further more preferably 7.0 mmol / g or less, and further more preferably 5.0 mmol / g or less. In addition, the cationic charge density of component (A) is preferably 0.1 mmol / g or more and 20 mmol / g or less, more preferably 0.2 mmol / g or more and 15 mmol / g or less, 0.2 mmol / g or more and 12 mmol / g or less, further more preferably 0.3 mmol / g or more and 10 mmol / g or less, further more preferably 0.3 mmol / g or more and 7.0 mmol / g or less, and further more preferably 0.5 mmol / g or more and 5.0 mmol / g or less.

[0069] The cationic charge density of component (A) is the molar number of cationic groups contained per 1 g of polymer. In addition, when at least a part of the cationic groups of component (A) are in the form of neutralized salts, the molar number of cationic groups also includes the molar number of cationic groups in the form of salts.

[0070] Furthermore, as the component (A), two or more polymers may be used. In this case, the cationic charge density of the component (A) is determined by calculating a weighted value from the cationic charge density and the blending amount of each polymer.

[0071] As the component (A), any of natural polymers such as cationized polysaccharides or cationized products thereof, and synthetic polymers can be used. However, synthetic polymers are preferred from the viewpoint of easy availability.

[0072] Specific examples of the polymer used as component (A) include the following polymers having a viscosity of 1% by mass aqueous solution at 30° C. of 1,000 mPa·s or more, such as cationized polyvinyl alcohol, polyethylene imine, methacryloyl ethyl trimethyl ammonium salt polymer, quaternized dialkylaminoalkyl (meth) acrylate polymer, diallyl quaternized ammonium salt polymer, methacrylamide propyl trimethyl ammonium salt polymer, vinyl imidazolium trichloride-vinyl pyrrolidone copolymer (polyquaternium-16), vinyl pyrrolidone-(meth) acrylic acid alkyl amino ester copolymer, vinyl pyrrolidone-(meth) acrylic acid alkyl amino ester-vinyl caprolactam copolymer, alkyl acrylamide-(meth) acrylic acid ester-alkyl amino alkyl acrylamide-polyethylene glycol (meth) acrylic acid ester copolymer, adipic acid-dimethylaminohydroxypropyl ethylenetriamine copolymer, and the like, and one or more of these can be used. In addition, in the present specification, "(meth) acrylic acid" means acrylic acid or methacrylic acid, and "(meth) acrylic acid ester" means acrylic acid ester or methacrylic acid ester.

[0073] Among the above, examples of methacryloylethyltrimethylammonium salt polymers include methacryloylethyltrimethylammonium chloride polymer (Polyquaternium-37), methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (Polyquaternium-49), and methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-2-hydroxyethyl methacrylate copolymer (Polyquaternium-48).

[0074] Examples of the quaternized dialkylaminoalkyl (meth)acrylate polymer include vinyl pyrrolidone-N,N-dimethylaminoethyl methacrylate diethylsulfate copolymer (Polyquaternium-11), and N,N-dimethylaminoethyl methacrylate diethylsulfate-N,N-dimethylacrylamide-polyethylene glycol dimethacrylate copolymer (Polyquaternium-52).

[0075] Examples of the diallyl quaternized ammonium salt polymer include dimethyldiallylammonium chloride polymer (polyquaternium-6), dimethyldiallylammonium chloride-acrylic acid copolymer (polyquaternium-22), dimethyldiallylammonium chloride-acrylamide copolymer (polyquaternium-7), and acrylamide-acrylic acid-dimethyldiallylammonium chloride copolymer (polyquaternium-39).

[0076] In addition, examples of the methacrylamide propyl trimethylammonium salt polymer include methacrylamide propyl trimethylammonium chloride polymer, vinyl pyrrolidone-methacrylamide propyl trimethylammonium chloride copolymer, acrylic acid-methyl acrylate-methacrylamide propyl trimethylammonium chloride copolymer (polyquaternium-47), acrylic acid-acrylamide-methacrylamide propyl trimethylammonium chloride copolymer (polyquaternium-53), and the like.

[0077] From the viewpoint of improving the film-forming ability, improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, and improving moisture resistance, component (A) is preferably a polymer containing a structural unit represented by the following general formula (1).

[0078]

[0079] In formula (1), R 1 is a hydrogen atom or a methyl group, R 2 ~R 4 Each independently represents an alkyl group having 1 to 4 carbon atoms. X represents -O- or -NH-, and m represents a number of 1 to 4.

[0080] R in the general formula (1) 1 Preferably, methyl, R 2 ~R 4 Each independently is preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, and still more preferably a methyl group.

[0081] In the general formula (1), X is preferably -O-, and m is preferably 1 or more and 3 or less, and more preferably 2 or more and 3 or less.

[0082] Examples of the structural unit represented by the general formula (1) include one or more structural units derived from methacryloylethyltrimethylammonium salt, structural units derived from N,N-dimethylaminoethylmethacrylate diethylsulfate, and structural units derived from methacrylamidopropyltrimethylammonium salt, and preferably one or more structural units derived from methacryloylethyltrimethylammonium salt and N,N-dimethylaminoethylmethacrylate diethylsulfate.

[0083] Component (A) may also contain a polymer of other structural units other than the structural unit represented by the general formula (1). Examples of such other structural units include structural units derived from vinyl monomers such as vinyl pyrrolidone, amphoteric monomers such as (meth)acryloylethyl dimethyl betaine, alkyl (meth)acrylates, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, and acrylamides such as N,N-dimethylacrylamide. In addition, component (A) may also be a cross-linked polymer cross-linked by polyethylene glycol di(meth)acrylate or the like.

[0084] In component (A), from the viewpoint of improving the film-forming ability, improving the texture-improving effect of the treated object and the sustainability of the effect, and improving the tangling-inhibiting effect of the fibers for hair or hair ornament products, especially when used for treating the fibers for hair or hair ornament products and the sustainability of the effect, the content of the structural unit represented by the general formula (1) is preferably 8.0 mol% or more, more preferably 10 mol% or more, and 100 mol% or less, in the total structural units constituting component (A).

[0085] Component (A) can be used alone or in combination of two or more. Among the above, component (A) is preferably one or more selected from methacryloylethyltrimethylammonium salt polymers and quaternized dialkylaminoalkyl (meth)acrylate polymers, and more preferably methacryloylethyltrimethylammonium chloride polymers (polyquaternium-37), methacryloylethyldimethylbetaine-methacryloylethyltrimethyl chloride polymers, from the viewpoint of easily making the viscosity of a 1 mass % aqueous solution at 30°C or more a specific value, improving the texture improvement effect of the treated object and the sustainability of the effect, improving the tangling suppression effect of hair or fibers for hair accessories when used for hair or fibers for hair accessories and the sustainability of the effect, improving moisture resistance, and improving the stability of the composition. Preferably, the present invention is at least one of ammonium-methoxy polyethylene glycol methacrylate copolymer (polyquaternium-49), methacryloylethyl dimethyl betaine-methacryloylethyl trimethyl ammonium chloride-2-hydroxyethyl methacrylate copolymer (polyquaternium-48), and N,N-dimethylaminoethyl methacrylate diethyl sulfate-N,N-dimethylacrylamide-dimethacrylate polyethylene glycol copolymer (polyquaternium-52), and more preferably at least one of methacryloylethyl trimethyl ammonium chloride polymer (polyquaternium-37) and N,N-dimethylaminoethyl methacrylate diethyl sulfate-N,N-dimethylacrylamide-dimethacrylate polyethylene glycol copolymer (polyquaternium-52).

[0086] As component (A), commercially available polymers may also be used. Specific examples thereof include Cosmedia Ultragel 300 (polyquaternium-37, cationic charge density: 4.81 mmol / g) manufactured by BASF JAPAN Co., Ltd., Sofcare KG-101W-E (polyquaternium-52, cationic charge density: 0.83 mmol / g), and Sofcare KG-301W (polyquaternium-52, cationic charge density: 1.84 mmol / g) manufactured by Kao Corporation.

[0087] (Component (B): anionic polymer)

[0088] Component (B) is a polymer that can form a polyion complex by interacting with component (A). In this specification, "anionic polymer" refers to a polymer having anionic groups and substantially no cationic groups and amphoteric groups. "Substantially no cationic groups and amphoteric groups" means that the molar amount of cationic groups and amphoteric groups relative to anionic groups is preferably less than 0.1%.

[0089] As the anionic group possessed by component (B), preferably an acidic group such as carboxyl, sulfonic acid, phosphoric acid, etc., with respect to the viewpoint of easily forming a polyion complex by interaction with component (A) and the viewpoint of availability, more preferably a carboxyl. In addition, in component (B), at least a part of the anionic group can also be in a state of a salt through neutralization.

[0090] <Component (B1): Crosslinked polymer containing a structural unit derived from (meth)acrylic acid, anionic polysaccharide>

[0091] From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, improving moisture resistance, and improving the stability of the composition, component (B) preferably contains (B1) at least one selected from a cross-linked polymer containing a structural unit derived from (meth)acrylic acid and anionic polysaccharides.

[0092] Among the components (B1), examples of the cross-linked polymer containing a structural unit derived from (meth)acrylic acid include homopolymers or copolymers of (meth)acrylic acid having a cross-linked structure, or salts thereof. The cross-linked structure referred to herein refers to a three-dimensional network structure formed by polymer chains, which are the main structure of the polymer, being linked within the polymer chain or between polymer chains. There is no particular limitation on the method for forming the cross-linked structure, and examples thereof include: a cross-linked structure formed by a method such as polycondensation or free radical polymerization in which cross-linking is performed while polymerization is performed, or a method in which the polymer chains are cross-linked after polymerization.

[0093] Examples of the homopolymer of (meth)acrylic acid include polyacrylic acid, polymethacrylic acid, and salts thereof.

[0094] Examples of the above-mentioned (meth)acrylic acid copolymers include (meth)acrylic acid / maleic acid copolymers, (meth)acrylic acid / itaconic acid copolymers, (meth)acrylic acid / fumaric acid copolymers, (meth)acrylic acid / vinyl acetate copolymers, (meth)acrylic acid / (meth)acrylic acid alkyl ester copolymers, (meth)acrylic acid / 2-hydroxyethyl methacrylate copolymers, acrylic acid / alkyl acrylate / (N-alkyl)acrylamide copolymers, and salts thereof. One or more of these can be used.

[0095] Among the above, the copolymer of (meth)acrylic acid is preferably (meth)acrylic acid / alkyl (meth)acrylate, and more preferably acrylic acid / alkyl acrylate. As the alkyl (meth)acrylate, there can be mentioned alkyl (meth)acrylates having an alkyl group with a carbon number of preferably 1 or more, more preferably 4 or more, further preferably 8 or more, and preferably 40 or less, more preferably 36 or less, further preferably 32 or less.

[0096] Specific examples of the cross-linked polymer containing a structural unit derived from (meth)acrylic acid include carboxyvinyl polymer or its salt, (acrylate / alkyl acrylate (C10-30)) cross-linked polymer, (sodium acrylate / acryloyldimethyl taurine / dimethyl acrylamide) cross-linked polymer, and acrylate cross-linked polymer-4.

[0097] Among component (B1), examples of anionic polysaccharides include polysaccharides having a carboxyl group (hyaluronic acid, alginic acid, pectic acid, carboxymethyl cellulose, xanthan gum, etc.), sulfates of polysaccharides (carrageenan, keratan sulfate, dermatan sulfate, sulfated starch, heparin, heparan sulfate), and salts thereof. One or more of these can be used.

[0098] Among the above, from the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, and improving the tangling-inhibiting effect of hair or fibers for hair ornament products and the sustainability of the effect, especially when used for treating hair or fibers for hair ornament products, the anionic polysaccharide is preferably a polysaccharide having a carboxyl group or a salt thereof, more preferably alginic acid, carboxymethyl cellulose or a salt thereof, and still more preferably alginic acid or a salt thereof.

[0099] When the component (B1) is a salt, examples of the salt include alkali metal salts such as sodium salts and potassium salts, and alkaline earth metal salts. From the viewpoint of availability, alkali metal salts are preferred.

[0100] Among the above, from the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the fibers for hair or hair ornament products and the sustainability of the effect when used for treating the fibers for hair or hair ornament products, improving the moisture resistance, and improving the stability of the composition, component (B1) is preferably one or more selected from carboxyvinyl polymers, (acrylate / alkyl acrylate (C10-30)) crosslinked polymers, and anionic polysaccharides, more preferably anionic polysaccharides or salts thereof, and still more preferably alginic acid or salts thereof.

[0101] There is no particular limitation on the anionic charge density of component (B1), but from the viewpoint of easily forming a polyion complex through interaction with component (A), improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products, especially when used for treating hair or fibers for hair ornament products, and its sustainability, from the viewpoint of improving moisture resistance, and from the viewpoint of improving the stability of the composition, it is preferably 1.0 mmol / g or more, more preferably 2.0 mmol / g or more, and further preferably 3.5 mmol / g or more. From the viewpoint of improving the texture-enhancing effect of the treated object and its sustainability, and improving the tangling-inhibiting effect of hair or fibers for hair ornament products, especially when used for treating hair or fibers for hair ornament products, and its sustainability, it is preferably 25 mmol / g or less, more preferably 20 mmol / g or less, and further preferably 15 mmol / g or less. The anion charge density of component (B1) is preferably from 1.0 mmol / g to 25 mmol / g, more preferably from 2.0 mmol / g to 20 mmol / g, and even more preferably from 3.5 mmol / g to 15 mmol / g.

[0102] The anionic charge density of component (B1) is the number of moles of anionic groups contained per 1 g of polymer. In addition, when at least a part of the anionic groups of component (B1) are in the form of neutralized salts, the number of moles of anionic groups also includes the number of moles of anionic groups in the form of salts.

[0103] Two or more polymers may be used as the component (B1). In this case, the anionic charge density of the component (B1) is determined by calculating a weighted average value from the anionic charge densities and blending amounts of the respective polymers.

[0104] When component (B1) is an anionic polysaccharide, from the viewpoint of improving the film-forming ability, the weight average molecular weight (Mw) is preferably 2,000 or more, more preferably 10,000 or more, further preferably more than 30,000, and further more preferably 50,000 or more. In addition, from the viewpoint of easily forming a polyion complex by interaction with component (A), improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, improving the moisture resistance, and improving the stability of the composition, it is preferably 3.5 million or less, and more preferably 3 million or less. The weight average molecular weight (Mw) of the anionic polysaccharide as component (B1) is preferably 2,000 to 3,500,000, more preferably 10,000 to 3,000,000, further preferably more than 30,000 to 3,000,000, and still more preferably 50,000 to 3,000,000.

[0105] The weight average molecular weight of the component (B1) can be measured by gel permeation chromatography (GPC).

[0106] From the viewpoint of improving the film-forming ability, facilitating the formation of a polyion complex by interaction with component (A), improving the texture-improving effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, improving moisture resistance, and improving the stability of the composition, the content of component (B1) in component (B) is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, further more preferably 80% by mass or more, and is 100% by mass or less.

[0107] <Component (B2): Anionic polymer other than component (B1)>

[0108] From the viewpoint of further improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, and improving moisture resistance, component (B) preferably further contains (B2) an anionic polymer other than the above-mentioned component (B1).

[0109] It is believed that component (B2) can form hydrogen bonds with the nonionic polymer (C), thereby fixing component (C) in the cross-linked structure of the polyion complex formed by component (A)-component (B). It is believed that due to this effect, even if the object is rinsed or washed after being treated with the above composition, component (C) will not be rinsed away and will easily remain in the film, thereby improving the sustainability of the treatment effect.

[0110] The molecular weight of component (B2) is preferably 1,000 or more, more preferably 2,000 or more, further preferably 5,000 or more, and further preferably 10,000 or more, and preferably 50,000 or less, more preferably 40,000 or less, and further preferably 30,000 or less, from the viewpoint of contributing to the fixation of component (C), further improving the texture-enhancing effect of the treated object and the sustainability of the effect, particularly when used for treating hair or hair ornament fibers and the sustainability of the effect, and improving moisture resistance. Furthermore, the molecular weight of component (B2) is preferably 1,000 or more and 50,000 or less, more preferably 1,000 or more and 30,000 or less, further preferably 2,000 or more and 30,000 or less, further more preferably 5,000 or more and 30,000 or less, and further more preferably 10,000 or more and 30,000 or less.

[0111] The "molecular weight" referred to herein refers to a weight average molecular weight, which can be measured by gel permeation chromatography (GPC).

[0112] Component (B2) is preferably a polymer having a carboxyl group having a molecular weight of 1,000 to 50,000, more preferably 1,000 to 30,000, and more preferably a non-crosslinked polymer having a molecular weight of 1,000 to 30,000 containing a structural unit derived from (meth)acrylic acid.

[0113] Examples of the non-crosslinked polymer containing a structural unit derived from (meth)acrylic acid and suitable for use as the component (B2) include, in addition to poly(meth)acrylic acid, (meth)acrylic acid / maleic acid copolymers, (meth)acrylic acid / itaconic acid copolymers, (meth)acrylic acid / fumaric acid copolymers, (meth)acrylic acid / vinyl acetate copolymers, (meth)acrylic acid / (meth)acrylic acid alkyl ester copolymers, (meth)acrylic acid / methacrylic acid 2-hydroxyacetate copolymers, acrylic acid / alkyl acrylate / (N-alkyl)acrylamide copolymers, and salts thereof. One or more of these can be used.

[0114] Examples of polymers having a carboxyl group other than those described above that are preferably used as component (B2) include polymaleic acid, maleic acid / diisobutylene copolymers, maleic acid / styrene copolymers, benzoic acid formaldehyde condensates, benzoic acid / phenol / formaldehyde condensates, and salts thereof.

[0115] Among the above, from the viewpoint of further improving the texture-enhancing effect of the treated object and the sustainability of the effect, from the viewpoint of improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, and from the viewpoint of improving moisture resistance, component (B2) is preferably at least one selected from poly(meth)acrylic acid, (meth)acrylic acid / alkyl (meth)acrylate copolymers, and salts thereof.

[0116] Examples of the poly(meth)acrylic acid or a salt thereof include polyacrylic acid, polymethacrylic acid, and salts thereof, and polyacrylic acid or a salt thereof is preferred.

[0117] As the (meth)acrylic acid / (meth)acrylic acid alkyl ester copolymer or its salt, acrylic acid / acrylic acid alkyl ester or its salt is more preferred. As the (meth)acrylic acid alkyl ester, there can be mentioned alkyl (meth)acrylic acid esters in which the number of carbon atoms in the alkyl group is preferably 1 or more, more preferably 4 or more, further preferably 8 or more, further more preferably 12 or more, and preferably 40 or less, more preferably 36 or less, further preferably 32 or less, further more preferably 24 or less.

[0118] The (meth)acrylic acid / (meth)acrylic acid alkyl ester is preferably acrylic acid / alkyl acrylate, more preferably one or more selected from (acrylic acid / octyl acrylate) copolymers and (acrylic acid / stearyl acrylate) copolymers, and still more preferably (acrylic acid / stearyl acrylate) copolymers.

[0119] When the component (B2) is a salt, examples of the salt include alkali metal salts such as sodium salts and potassium salts, and alkaline earth metal salts. From the viewpoint of availability, alkali metal salts are preferred.

[0120] There is no particular limitation on the anionic charge density of component (B2), but from the viewpoint of further improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, and improving moisture resistance, it is preferably 1.0 mmol / g or more, more preferably 3.0 mmol / g or more, and further preferably 5.0 mmol / g or more, and preferably 25 mmol / g or less, more preferably 20 mmol / g or less, and further preferably 15 mmol / g or less. Furthermore, the anionic charge density of component (B2) is preferably 1.0 mmol / g or more and 25 mmol / g or less, more preferably 3.0 mmol / g or more and 20 mmol / g or less, and further preferably 5.0 mmol / g or more and 15 mmol / g or less.

[0121] Two or more polymers may be used as the component (B2). In this case, the anionic charge density of the component (B2) can be determined by calculating a weighted average value from the anionic charge densities and blending amounts of the respective polymers.

[0122] When component (B) contains component (B2), the content of component (B2) in component (B) is preferably 1% by mass or more, more preferably 2% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, and preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, and even more preferably 20% by mass or less, from the viewpoint of further improving the texture-enhancing effect of the treated object and the sustainability of the effect, especially improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, and improving moisture resistance. In addition, the content of component (B2) in component (B) is preferably 1% by mass or more and 50% by mass or less, more preferably 2% by mass or more and 40% by mass or less, even more preferably 3% by mass or more and 30% by mass or less, and even more preferably 5% by mass or more and 20% by mass or less.

[0123] In addition, when the component (B) contains the component (B1) and the component (B2), the mass ratio of the component (B2) to the total amount of the component (B1) and the component (B2) [(B2) / {(B1)+(B2)}] is preferably 0.01 or more, more preferably 0.02 or more, further preferably 0.05 or more, and further preferably 0.08 or more, from the viewpoint of further improving the texture-enhancing effect of the treated object and the sustainability of the effect, especially improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for the treatment of the hair or hair ornament fiber and the sustainability of the effect, and improving the moisture resistance. From the viewpoint of the ease of forming a polyion complex with the component (A), it is preferably 1.0 or less, more preferably 0.80 or less, further preferably 0.50 or less, and further preferably 0.30 or less. The mass ratio [(B2) / {(B1)+(B2)}] is preferably 0.01 to 1.0, more preferably 0.02 to 0.80, further preferably 0.05 to 0.50, and still further preferably 0.08 to 0.30.

[0124] (Component (C): nonionic polymer)

[0125] In the present specification, the "nonionic polymer" refers to a polymer that does not substantially have a cationic group, an anionic group, or an amphoteric group as an ionic group.

[0126] Component (C) includes polyalkylene glycol or derivatives thereof, polymers containing structural units derived from vinylpyrrolidone, polymers containing structural units derived from (meth)acrylate, polyvinyl alcohol, polyacrylamide, polycaprolactam, etc., and one or more of these can be used.

[0127] Examples of the polyalkylene glycol include homopolymers or copolymers of alkylene glycols in which the number of carbon atoms of the alkylene group is 2 to 6, preferably 2 to 4, and more preferably 2 to 3. Specific examples thereof include polyethylene glycol, polypropylene glycol, polytrimethylene ether glycol, polytetramethylene ether glycol, polyethylene glycol-polypropylene glycol copolymer (polyoxyethylene polyoxypropylene glycol), polyethylene glycol-polytrimethylene ether glycol copolymer, polyethylene glycol-polytetramethylene ether glycol copolymer, polypropylene glycol-polytetramethylene ether glycol copolymer, and the like. Among these, from the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, improving moisture resistance, and the viewpoint of availability, preferably at least one selected from polyethylene glycol, polypropylene glycol, and polyethylene glycol-polypropylene glycol copolymers, and more preferably at least one selected from polyethylene glycol and polyethylene glycol-polypropylene glycol copolymers.

[0128] Examples of the polyalkylene glycol derivatives include terminal modified products of the above-mentioned polyalkylene glycols, for example, polyalkylene glycol monoalkyl ethers, polyalkylene glycol dialkyl ethers, polyalkylene glycol monoaryl ethers, polyalkylene glycol diaryl ethers, polyalkylene glycol monofatty acid esters, polyalkylene glycol difatty acid esters, polyalkylene glycol diglycidyl ethers, etc. Among these, from the viewpoint of improving the texture improvement effect of the treated object and the sustainability of the effect, improving the tangling suppression effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, improving the moisture resistance, and the availability, preferably one or more selected from the group consisting of polyalkylene glycol monoalkyl ethers, polyalkylene glycol dialkyl ethers, polyalkylene glycol monofatty acid esters, and polyalkylene glycol difatty acid esters, and more preferably one or more selected from the group consisting of polyalkylene glycol monofatty acid esters and polyalkylene glycol difatty acid esters.

[0129] The number of carbon atoms of the alkyl group in the monoalkyl ether or dialkyl ether of the polyalkylene glycol and the number of carbon atoms of the fatty acid in the monofatty acid ester or difatty acid ester of the polyalkylene glycol are preferably 1 to 36, more preferably 4 to 32, further preferably 8 to 24, and further more preferably 12 to 22. In addition, the number of carbon atoms of the aryl group in the monoaryl ether or diaryl ether of the polyalkylene glycol is preferably 6 to 36, more preferably 6 to 32, further preferably 6 to 24, and further more preferably 6 to 22.

[0130] Specific examples of the polyalkylene glycol derivatives include polyethylene glycol monomethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol monobutyl ether, polyethylene glycol dibutyl ether, polyethylene glycol monooctyl ether, polyethylene glycol monodecyl ether, polyethylene glycol monododecyl ether, polyethylene glycol monotridecyl ether, polyethylene glycol-bisphenol A ether, polyethylene glycol dilaurate, polyethylene glycol distearate (distearate polyethylene glycol), polyethylene glycol diglycidyl ether, polyethylene glycol-polypropylene glycol-monomethyl ether, polyethylene glycol-polypropylene glycol-dimethyl ether, Polyethylene glycol-polypropylene glycol-monobutyl ether, polyethylene glycol-polypropylene glycol-dibutyl ether, polyethylene glycol-polypropylene glycol-monooctyl ether, polyethylene glycol-polypropylene glycol-monodecyl ether, polyethylene glycol-polypropylene glycol-monododecyl ether, polyethylene glycol-polypropylene glycol-monotridecyl ether, polyethylene glycol-polypropylene glycol-bisphenol A ether, polyethylene glycol-polypropylene glycol-dilaurate, polyethylene glycol-polypropylene glycol distearate, polyethylene glycol-polypropylene glycol-diglycidyl ether, etc., and one or more of these can be used.

[0131] Examples of the polymer containing a structural unit derived from vinyl pyrrolidone include homopolymers of vinyl pyrrolidone and copolymers of vinyl pyrrolidone and a nonionic monomer, and specific examples thereof include polyvinyl pyrrolidone, vinyl pyrrolidone / vinyl acetate copolymers, and vinyl pyrrolidone / methacrylamide / vinylimidazole copolymers.

[0132] Examples of the polymer containing a structural unit derived from (meth)acrylate include homopolymers of (meth)acrylate and copolymers of (meth)acrylate with nonionic monomers such as (meth)acrylamide, dimethylacrylamide, vinyl acetate, and vinyl methyl ether. Examples of (meth)acrylate include hydroxyalkyl (meth)acrylates, alkyl (meth)acrylates, and the like in addition to the above-mentioned alkyl (meth)acrylates.

[0133] Specific examples of the polymer containing a structural unit derived from a (meth)acrylate include a (dimethylacrylamide / hydroxyethyl acrylate / methoxyethyl acrylate) copolymer and a (hydroxyethyl acrylate / methoxyethyl acrylate) copolymer.

[0134] Among the above, from the viewpoints of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, improving moisture resistance, and availability, component (C) is preferably at least one selected from polyalkylene glycol or its derivative, and a polymer containing a structural unit derived from vinyl pyrrolidone, more preferably at least one selected from polyethylene glycol, polypropylene glycol, a polyethylene glycol-polypropylene glycol copolymer, mono- or di-fatty acid esters thereof, and polyvinyl pyrrolidone, and further preferably at least one selected from polyethylene glycol, a polyethylene glycol-polypropylene glycol copolymer, mono- or di-fatty acid esters thereof, and polyvinyl pyrrolidone.

[0135] The weight average molecular weight (Mw) of component (C) is preferably 2,000 or more, more preferably 5,000 or more, and further preferably 8,000 or more, and preferably 2,000,000 or less, and more preferably 1,500,000 or less, from the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, especially when used for treating hair or fibers for hair ornament products and the sustainability of the effect, from the viewpoint of improving moisture resistance, and from the viewpoint of availability. In addition, the weight average molecular weight of component (C) is preferably 2,000 or more and 2,000,000 or less, more preferably 5,000 or more and 1,500,000 or less, and further preferably 8,000 or more and 1,500,000 or less.

[0136] The weight average molecular weight of the component (C) can be measured by gel permeation chromatography (GPC).

[0137] (Ingredient (D): acid)

[0138] (D) Acids help to stably form polyion complexes.

[0139] As component (D), an organic acid or an inorganic acid can be used, and an organic acid is preferred from the viewpoint of using the manufactured composition as a cosmetic composition. As the organic acid, carboxylic acid compounds and sulfonic acid compounds other than component (B) can be cited, and compounds with a molecular weight of 500 or less, more preferably 200 or less are preferred.

[0140] As carboxylic acid compounds, for example, there can be mentioned: aliphatic monocarboxylic acids having less than 4 carbon atoms, such as acetic acid, propionic acid, and butyric acid; aromatic monocarboxylic acids, such as benzoic acid; aliphatic dicarboxylic acids, such as malonic acid, succinic acid, glutaric acid, adipic acid, maleic acid, and fumaric acid; aromatic dicarboxylic acids, such as phthalic acid and isophthalic acid; polycarboxylic acids, such as polyglutamic acid; hydroxycarboxylic acids, such as lactic acid, malic acid, glycolic acid, hydroxyacrylic acid, glyceric acid, tartaric acid, and citric acid; acidic amino acids, such as glutamic acid and aspartic acid, etc.; one or more of these can be used.

[0141] Examples of the sulfonic acid compound include aliphatic sulfonic acids such as methanesulfonic acid and ethanesulfonic acid; and aromatic sulfonic acids such as p-toluenesulfonic acid and naphthalenesulfonic acid. One or more of these may be used.

[0142] From the viewpoint of stably forming a polyion complex to produce a composition with higher stability, and from the viewpoint of using the produced composition as a cosmetic composition, the organic acid is preferably at least one selected from aliphatic dicarboxylic acids, hydroxycarboxylic acids, and aromatic sulfonic acids, more preferably at least one selected from succinic acid, lactic acid, malic acid, glycolic acid, p-toluenesulfonic acid, and naphthalenesulfonic acid, further preferably at least one selected from succinic acid and lactic acid, and further more preferably lactic acid.

[0143] In addition, when an organic acid is formulated, at least a portion thereof may be in the form of an organic acid salt. As the salt of the organic acid, from the viewpoint of use in a cosmetic composition or a fiber treatment composition for a headdress product, and from the viewpoint of easy availability, an alkali metal salt or an alkali metal salt of an organic acid is preferred, an alkali metal salt is more preferred, and one or more selected from a sodium salt and a potassium salt is further preferred, and a sodium salt is further preferred.

[0144] From the viewpoint of the formation difficulty of polyion complex and the stability of the composition, the ratio of organic acid salt in the total amount of organic acid and organic acid salt is preferably below 50 mass %, more preferably below 20 mass %, further preferably below 5 mass %, and may be 0 mass %. The ratio (mass %) of organic acid salt mentioned here refers to the mass % converted into organic acid.

[0145] (water)

[0146] As water, deionized water or distilled water is preferred. Alternatively, tap water, groundwater, etc. sterilized with hypochlorous acid or the like may be used within a range that does not impair the stability of the composition.

[0147] (oily ingredients)

[0148] The emulsified composition obtained by the production method of the present invention contains an oily component as an emulsion-forming component in addition to (A) a cationic polymer, (B) an anionic polymer, (C) a nonionic polymer, (D) an acid, and water.

[0149] As the oily component, it is preferred to include an ionic surfactant and an amphiphilic substance having a hydrophobic group from the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, and improving moisture resistance. In particular, when the emulsified composition is used as a hair cosmetic composition, preferably a hair conditioner, a hair conditioner, a hair care agent, or a styling agent, the ionic surfactant is preferably (E) a cationic surfactant, and the amphiphilic substance having a hydrophobic group is preferably (F) a higher alcohol. That is, the oily component contained in the emulsified composition preferably includes (E) a cationic surfactant and (F) a higher alcohol. Furthermore, the emulsified composition may contain (G) an oily agent and (H) an aqueous medium as arbitrary components.

[0150] [Ingredient (E): cationic surfactant]

[0151] (E) The cationic surfactant is an oily component contained in the oil phase of the emulsified composition.

[0152] Examples of the cationic surfactant include (i) alkyltrimethylammonium salts, (ii) alkoxyalkyltrimethylammonium salts, (iii) dialkyldimethylammonium salts, (iv) alkylamidealkyltrimethylammonium salts, (v) alkyldimethylamines and salts thereof, (vi) alkoxyalkyldimethylamines and salts thereof, and (vii) alkylamidealkyldimethylamines and salts thereof.

[0153] (i) The alkyltrimethylammonium salts are preferably alkyltrimethylammonium salts having an alkyl group having 12 to 24 carbon atoms, more preferably 16 to 24 carbon atoms, and specifically include cetyltrimethylammonium chloride, steartrimethylammonium chloride, behentrimethylammonium chloride, and the like.

[0154] (ii) The alkoxyalkyltrimethylammonium salt is preferably an alkoxyalkyltrimethylammonium salt having an alkoxy group having 12 to 22 carbon atoms, more preferably 16 to 20 carbon atoms. Specific examples include stearoxypropyltrimethylammonium chloride, stearoxyethyltrimethylammonium chloride, and stearoxyhydroxypropyltrimethylammonium chloride.

[0155] (iii) The dialkyldimethylammonium salt preferably includes a dialkyldimethylammonium salt having an alkyl group having 12 to 22 carbon atoms, more preferably 16 to 20 carbon atoms, and specifically, distearyldimethylammonium chloride and the like are mentioned.

[0156] (iv) The alkylamide alkyltrimethylammonium salt preferably includes an alkylamide alkyltrimethylammonium salt having an alkyl group having 11 to 21 carbon atoms, more preferably 13 to 19 carbon atoms, and specifically includes palmitamidopropyltrimethylammonium chloride.

[0157] (v) Alkyldimethylamine, (vi) alkoxyalkyldimethylamine, and (vii) alkylamidealkyldimethylamine react with an acid to form a tertiary amine salt, thereby forming a cationic surfactant.

[0158] The alkyl group in (v) alkyldimethylamine and its salt, and the alkoxy group in (vi) alkoxyalkyldimethylamine and its salt are preferably an alkyl group having 12 to 22 carbon atoms, more preferably 16 to 20 carbon atoms.

[0159] (vii) The alkyl group of the alkylamide moiety in the alkylamide alkyldimethylamine and its salt is preferably an alkyl group having 11 to 21 carbon atoms, more preferably 15 to 19 carbon atoms.

[0160] The amines of (v) to (vii) may be reacted with an acid in advance and formulated in the emulsified composition in the form of a salt. Alternatively, they may be formulated directly in the emulsified composition in the form of an amine, and an acid may be further formulated in the emulsified composition to form a salt in the composition. Therefore, the above amines and their salts are defined as cationic surfactants herein. In addition, the content or formulation amount thereof is converted to the mass of the above amine.

[0161] As salts of the amines of (v) to (vii), salts formed by organic acids or inorganic acids can be cited. As organic acids, for example, monocarboxylic acids such as acetic acid and propionic acid; dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, maleic acid, fumaric acid, and phthalic acid; polycarboxylic acids such as polyglutamic acid; hydroxycarboxylic acids such as glycolic acid, lactic acid, hydroxyacrylic acid, glyceric acid, malic acid, tartaric acid, and citric acid; acidic amino acids such as glutamic acid and aspartic acid, etc. As inorganic acids, for example, hydrochloric acid, sulfuric acid, phosphoric acid, etc. can be cited. Of these, organic acids are preferred, and more preferably, one or more selected from dicarboxylic acids, hydroxycarboxylic acids, and acidic amino acids are more preferred. As dicarboxylic acids, more preferably, one or more selected from maleic acid and succinic acid are more preferred. As hydroxycarboxylic acids, more preferably, one or more selected from glycolic acid, lactic acid, and malic acid are more preferred. As acidic amino acids, more preferably, glutamic acid is more preferred.

[0162] (v) Alkyldimethylamine and salts thereof include N,N-dimethylbehenylamine, N,N-dimethylstearylamine, and organic acid salts thereof, and lactic acid salts of N,N-dimethylbehenylamine and glycolic acid salts of N,N-dimethylstearylamine are preferred.

[0163] (vi) Alkoxyalkyldimethylamines and salts thereof include N,N-dimethyl-3-hexadecyloxypropylamine, N,N-dimethyl-3-octadecyloxypropylamine, and organic acid salts thereof, preferably N,N-dimethyl-3-hexadecyloxypropylamine or a lactate thereof, and N,N-dimethyl-3-octadecyloxypropylamine (stearyloxypropyldimethylamine) or a lactate thereof.

[0164] (vii) Alkylamide alkyldimethylamine and its salt include N-[3-(dimethylamino)propyl]behenamide, N-[3-(dimethylamino)propyl]stearamide, and organic acid salts thereof, preferably N-[3-(dimethylamino)propyl]behenamide lactate and N-[3-(dimethylamino)propyl]stearamide glycolate.

[0165] The component (E) can be used alone or in combination of two or more.

[0166] Among the above, as component (E), from the viewpoint of further improving the touch of the treated object, preferably at least one selected from (i) alkyltrimethylammonium salts, (ii) alkoxyalkyltrimethylammonium salts, (iii) dialkyldimethylammonium salts, (iv) alkylamidealkyltrimethylammonium salts, (v) alkyldimethylamines and salts thereof, (vi) alkoxyalkyldimethylamines and salts thereof, and (vii) alkylamidealkyldimethylamines and salts thereof, and more preferably at least one selected from (i) alkyltrimethylammonium salts and (vi) alkoxyalkyldimethylamines. The present invention further preferably comprises at least one selected from cetyl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, behenyl trimethyl ammonium chloride, N,N-dimethyl-3-hexadecyloxypropylamine or its lactate, and N,N-dimethyl-3-octadecyloxypropylamine (stearyloxypropyl dimethylamine) or its lactate, and further preferably comprises at least one selected from behenyl trimethyl ammonium chloride and N,N-dimethyl-3-octadecyloxypropylamine (stearyloxypropyl dimethylamine) or its lactate.

[0167] [Component (F): higher alcohol]

[0168] (F) The higher alcohol is an oily component contained in the oil phase of the emulsified composition.

[0169] Component (F) includes aliphatic monohydric alcohols having 12 or more carbon atoms, preferably 12 or more and 22 or less carbon atoms. The higher alcohol includes at least one selected from lauryl alcohol, cetyl alcohol, myristyl alcohol, oleyl alcohol, stearyl alcohol, isostearyl alcohol, 2-octyldodecanol, behenyl alcohol, and cetearyl alcohol.

[0170] Among the above, from the viewpoint of further improving the touch of the treatment object, at least one selected from cetyl alcohol, myristyl alcohol, stearyl alcohol, and behenyl alcohol is preferred.

[0171] [Ingredient (G): oil]

[0172] (G) The oil agent is an oily component contained in the oil phase of the emulsion composition except for the components (E) and (F).

[0173] As component (G), there can be mentioned (a) silicone oil, (b) ester oil, (c) ether oil, (d) hydrocarbon oil, (e) higher fatty acid, (f) waxes, etc., and one or more of these can be used. Among the above, from the viewpoint of further improving the touch of the treated object, it is preferably one or more selected from (a) silicone oil, (b) ester oil, (d) hydrocarbon oil, and (e) higher fatty acid, and more preferably (a) silicone oil.

[0174] (a) The silicone oil is preferably at least one selected from dimethylpolysiloxane (polydimethylsiloxane), dimethylpolysiloxanol (dimethylpolysiloxane having a terminal hydroxyl group), methylphenylpolysiloxane, and modified silicone.

[0175] Examples of modified silicones include amino-modified silicones (dimethyl polysiloxanes having an amino group such as aminodimethyl polysiloxane), polyether-modified silicones, aminopolyether-modified silicones (silicone having an amino group and a polyether structure), glycerin-modified silicones, carboxyl-modified silicones, fatty acid-modified silicones, alcohol-modified silicones, aliphatic alcohol-modified silicones, epoxy-modified silicones, fluorine-modified silicones, and alkyl-modified silicones.

[0176] Among the above, from the viewpoint of further improving the touch of the treated object, the silicone oil (a) is preferably at least one selected from dimethylpolysiloxane, dimethylpolysiloxanol, methylphenylpolysiloxane, and modified silicone, more preferably at least one selected from dimethylpolysiloxane, dimethylpolysiloxanol, amino-modified silicone, polyether-modified silicone, and aminopolyether-modified silicone, and even more preferably at least one selected from dimethylpolysiloxane, amino-modified silicone, and aminopolyether-modified silicone.

[0177] (Component (H): aqueous medium)

[0178] (H) Aqueous medium refers to an aqueous medium other than water. Component (H) is an aqueous component and can be used in either an aqueous composition or an emulsified composition. In an emulsified composition, component (H) is usually contained in the aqueous phase, but can also be formulated in the oil phase in the emulsified composition.

[0179] Component (H) includes lower alcohols such as ethanol and isopropanol, and low molecular weight diols and triols having 6 or less carbon atoms such as 1,3-butanediol, glycerol, ethylene glycol, propylene glycol, and dipropylene glycol. One or more of these may be used.

[0180] (Content of each component in the composition)

[0181] From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, improving moisture resistance, and improving the stability of the composition, the content of each component in the aqueous composition and emulsified composition produced by the method of the present invention is preferably as follows.

[0182] From the viewpoint of the ease of forming a polyion complex, improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, and improving moisture resistance, the content of component (A) in the aqueous composition and the emulsified composition is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, further preferably 0.05% by mass or more, and further more preferably 0.1% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 3.0% by mass or less, more preferably 2.5% by mass or less, further preferably 2.0% by mass or less, further more preferably 1.5% by mass or less, and further more preferably 1.0% by mass or less. Furthermore, the content of component (A) in the aqueous composition and the emulsified composition is preferably from 0.01% by mass to 3.0% by mass, more preferably from 0.02% by mass to 2.5% by mass, even more preferably from 0.05% by mass to 2.0% by mass, even more preferably from 0.1% by mass to 1.5% by mass, even more preferably from 0.1% by mass to 1.0% by mass.

[0183] From the viewpoint of the ease of forming a polyion complex, improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, and improving moisture resistance, the content of component (B) in the aqueous composition and the emulsified composition is preferably 0.005% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.02% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 3.0% by mass or less, more preferably 2.0% by mass or less, even more preferably 1.5% by mass or less, even more preferably 1.0% by mass or less, even more preferably 0.5% by mass or less, even more preferably 0.3% by mass or less, even more preferably 0.2% by mass or less, and even more preferably 0.1% by mass or less. Furthermore, the content of component (B) in the aqueous composition and the emulsified composition is preferably from 0.005% by mass to 3.0% by mass, more preferably from 0.01% by mass to 2.0% by mass, even more preferably from 0.02% by mass to 1.5% by mass, even more preferably from 0.02% by mass to 1.0% by mass, even more preferably from 0.02% by mass to 0.5% by mass, even more preferably from 0.02% by mass to 0.3% by mass, even more preferably from 0.02% by mass to 0.3% by mass, even more preferably from 0.02% by mass to 0.2% by mass, even more preferably from 0.02% by mass to 0.1% by mass, even more preferably from 0.02% by mass to 0.1% by mass.

[0184] From the viewpoint of the ease of forming a polyion complex, improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, and improving moisture resistance, the total content of component (A) and component (B) in the aqueous composition and the emulsified composition is preferably 0.02% by mass or more, more preferably 0.04% by mass or more, further preferably 0.05% by mass or more, and further more preferably 0.1% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 5.0% by mass or less, more preferably 4.0% by mass or less, further preferably 3.0% by mass or less, and further more preferably 2.0% by mass or less. Furthermore, the total content of component (A) and component (B) in the aqueous composition and the emulsified composition is preferably from 0.02 mass % to 5.0 mass %, more preferably from 0.04 mass % to 4.0 mass %, further preferably from 0.05 mass % to 3.0 mass %, and even more preferably from 0.1 mass % to 2.0 mass %.

[0185] Regarding the content ratio of the component (A) to the component (B) in the aqueous composition and the emulsified composition, the mass ratio of the component (A) to the component (B) [(A) / (B)] is preferably 1.0 or more, more preferably 2.0 or more, even more preferably 3.0 or more, even more preferably 4.5 or more, even more preferably 4.7 or more, even more preferably 4.8 or more, even more preferably 5.0 or more, even more preferably 5.5 or more, even more preferably 6.0 or more, even more preferably 6.2 or more, even more preferably 6.5 or more, and is preferably 30 or less, more preferably 20 or less, even more preferably 18 or less, even more preferably 16 or less, even more preferably 15 or less, even more preferably 12 or less, even more preferably 10 or less, from the viewpoint of the difficulty of forming a polyion complex, the effect of improving the texture of the treated object and the sustainability of the effect, the effect of inhibiting tangling of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, and the viewpoint of improving moisture resistance. Furthermore, the mass ratio [(A) / (B)] is preferably 1.0 to 30, more preferably 1.0 to 20, further preferably 2.0 to 20, further preferably 3.0 to 20, further more preferably 4.5 to 20, further more preferably 4.7 to 18, further more preferably 4.8 to 18, further more preferably 5.0 to 18, further more preferably 5.5 to 16, further more preferably 6.0 to 16, further more preferably 6.2 to 15, further more preferably 6.5 to 15, further more preferably 6.5 to 12, further more preferably 6.5 to 10.

[0186] From the viewpoint of improving the texture improvement effect of the treated object and the persistence of the effect, improving the knotting inhibition effect of the hair or hair ornament fiber used for hair or hair ornament fiber treatment and its persistence, and improving the moisture resistance, the content of component (C) in the aqueous composition and the emulsified composition is preferably 0.02% by mass or more, more preferably 0.04% by mass or more, further preferably 0.05% by mass or more, and further more preferably 0.1% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 5.0% by mass or less, more preferably 4.0% by mass or less, further preferably 3.0% by mass or less, and further more preferably 2.0% by mass or less. In addition, the content of component (C) in the aqueous composition and the emulsified composition is preferably 0.02% by mass or more and 5.0% by mass or less, more preferably 0.04% by mass or more and 4.0% by mass or less, further preferably 0.05% by mass or more and 3.0% by mass or less, and further more preferably 0.1% by mass or more and 2.0% by mass or less.

[0187] From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the fibers for hair or hair ornament products when used for treating hair or hair ornament products and the sustainability of the effect, and improving moisture resistance, the mass ratio of the component (C) to the total amount of the component (A) and the component (B) in the aqueous composition and the emulsified composition [(C) / {(A)+(B)}] is preferably 0.2 or more, more preferably 0.3 or more, even more preferably 0.4 or more, even more preferably 0.5 or more, even more preferably 0.6 or more, even more preferably 0.8 or more, and is preferably 20 or less, more preferably 15 or less, even more preferably 10 or less, even more preferably 8.0 or less, even more preferably 5.0 or less, even more preferably 2.0 or less, and even more preferably 1.5 or less. Furthermore, the mass ratio [(C) / {(A)+(B)}] is preferably 0.2 to 20, more preferably 0.3 to 15, further preferably 0.4 to 10, further preferably 0.5 to 8.0, further more preferably 0.6 to 5.0, further more preferably 0.8 to 2.0, further more preferably 0.8 to 1.5.

[0188] From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, improving moisture resistance, and improving the stability of the composition, the content of component (D) in the aqueous composition and the emulsified composition is preferably 0.01% by mass or more, more preferably 0.02% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 3.0% by mass or less.

[0189] However, when the emulsified composition contains any one of (v) alkyldimethylamine and salts thereof, (vi) alkoxyalkyldimethylamine and salts thereof, and (vii) alkylamidealkyldimethylamine and salts thereof as (E) cationic surfactant, the content of component (D) in the emulsified composition may be an amount exceeding 3.0% by mass. This is because component (D) exists as a counter anion of the above amines, thereby improving the stability of the emulsified composition and improving the touch of the treated object.

[0190] When the component (D) is formulated in the state of an organic acid salt, the content of the component (D) is an amount converted into an organic acid.

[0191] From the viewpoint of improving the stability of the composition, the content of water in the aqueous composition and the emulsified composition is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and further more preferably 85% by mass or more. In addition, the content of water in the aqueous composition may be the remainder of components (A) to (D).

[0192] From the viewpoint of further improving the feel of the object to be treated, the content of the cationic surfactant (E) in the emulsified composition is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, more preferably 0.5% by mass or more, and further more preferably 1.0% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 10% by mass or less, more preferably 5.0% by mass or less, and further preferably 3.5% by mass or less. In addition, the content of the component (E) in the emulsified composition is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.2% by mass or more and 5.0% by mass or less, further preferably 0.5% by mass or more and 5.0% by mass or less, and further more preferably 1.0% by mass or more and 3.5% by mass or less.

[0193] From the viewpoint of further improving the touch of the object to be treated, the content of the (F) higher alcohol in the emulsified composition is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, more preferably 0.5% by mass or more, and further more preferably 1.0% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 15% by mass or less, more preferably 12% by mass or less, and further preferably 10% by mass or less. In addition, the content of the component (F) in the emulsified composition is preferably 0.1% by mass or more and 15% by mass or less, more preferably 0.2% by mass or more and 12% by mass or less, further preferably 0.5% by mass or more and 12% by mass or less, and further more preferably 1.0% by mass or more and 10% by mass or less.

[0194] When (G) oil is used in the emulsified composition, the content of component (G) in the emulsified composition is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and more preferably 0.5% by mass or more from the viewpoint of further improving the feel of the object to be treated. In addition, from the viewpoint of improving the stability of the composition, it is preferably 20% by mass or less, more preferably 10% by mass or less, and more preferably 5.0% by mass or less. In addition, the content of component (G) in the emulsified composition is preferably 0.1% by mass or more and 20% by mass or less, more preferably 0.2% by mass or more and 10% by mass or less, and more preferably 0.5% by mass or more and 10% by mass or less, and more preferably 0.5% by mass or more and 5.0% by mass or less.

[0195] When (H) aqueous medium is used in an aqueous composition or an emulsified composition, the content of component (H) in the aqueous composition or the emulsified composition is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, further preferably 0.5% by mass or more, preferably 10% by mass or less, more preferably 5.0% by mass or less. Furthermore, the content of component (H) in the composition is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.2% by mass or more and 5.0% by mass or less, further preferably 0.5% by mass or more and 5.0% by mass or less.

[0196] In addition, anionic surfactants, nonionic surfactants, amphoteric surfactants, aromatic ring-containing alcohols, antioxidants, antidandruff agents, vitamins, bactericides, anti-inflammatory agents, preservatives, chelating agents, moisturizers, pearlescent agents, ceramides, fragrances, plant extracts, ultraviolet absorbers, pH adjusters, etc. can also be formulated in the aqueous composition and the emulsified composition.

[0197] (pH value)

[0198] The pH value of the composition is preferably 3.0 or more, more preferably 3.2 or more, in terms of safety, as measured by the pH value of an aqueous solution obtained by diluting the composition 20 times with water at 25° C. In addition, from the viewpoint of improving the stability of the composition, it is preferably 7.5 or less, more preferably 7.0 or less, further preferably 6.0 or less, and further more preferably 5.0 or less.

[0199] The pH value can be measured using a pH meter by the method described in Examples.

[0200] Hereinafter, each step of the method for producing the composition of the present invention will be described. Steps 1 to 3 are common to the methods for producing an aqueous composition and an emulsified composition.

[0201] <Step 1: Preparation of mixture 1>

[0202] In step 1, a mixture 1 including (B) anionic polymer, (C) nonionic polymer and water is prepared.

[0203] In the preparation of the mixture 1, there is no particular restriction on the order of mixing the components (B), (C) and water. For example, the following methods may be mentioned: (1) a method of simultaneously adding the components (B) and (C) to water for dissolution or dispersion; (2) a method of preparing a solution in which the component (B) is dissolved or dispersed in water and a solution in which the component (C) is dissolved or dispersed in water, and mixing these; (3) a method of mixing a solution in which the component (B) is dissolved or dispersed in water with the component (C); (4) a method of mixing the component (B) with a solution in which the component (C) is dissolved or dispersed in water, etc. Among these, from the viewpoint of ease of manufacture, the method of (3) mixing a solution in which the component (B) is dissolved or dispersed in water with the component (C) is preferred.

[0204] In the above (2) or (3), when preparing a solution in which component (B) is dissolved or dispersed in water, component (B) may be dispersed in an aqueous medium other than water such as dipropylene glycol before being dissolved or dispersed in water.

[0205] In the above (2) to (4), as the solution formed by dissolving or dispersing component (B) or component (C) in water, a commercially available aqueous solution or aqueous dispersion may be used. In addition, for example, the reaction solution when component (B) or component (C) is produced using water as a reaction solvent may be used as the solution formed by dissolving or dispersing component (B) or component (C) in water.

[0206] The preparation of the mixture 1 in the step 1 can be performed using a known stirring device such as a homomixer and a mechanical stirrer.

[0207] In step 1, the temperature when preparing the mixture 1 is not particularly limited. From the viewpoint of improving the solubility or dispersibility of the component (B) and the component (C), it is preferably 40°C or higher, more preferably 45°C or higher, and even more preferably 50°C or higher. From the viewpoint of suppressing thermal degradation of the formulated components, it is preferably 90°C or lower, more preferably 80°C or lower, even more preferably 70°C or lower, and even more preferably 65°C or lower. Furthermore, the temperature when preparing the mixture 1 is preferably 40°C or higher and 90°C or lower, more preferably 45°C or higher and 80°C or lower, even more preferably 50°C or higher and 70°C or lower, and even more preferably 50°C or higher and 65°C or lower.

[0208] The mixing time for preparing the mixture 1 can be appropriately selected, and is preferably 1 minute or longer, more preferably 3 minutes or longer, and preferably 6 hours or shorter from the viewpoint of productivity.

[0209] From the viewpoint of improving the stability of the composition and the viewpoint of ease of manufacture, the total content of component (B) and component (C) in mixture 1 is preferably 0.03% by mass or more, more preferably 0.1% by mass or more, further preferably 0.3% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, further preferably 35% by mass or less.

[0210] In the case of a method for producing an aqueous composition or a method for producing an emulsified composition and having step 4-2, from the viewpoint of improving the stability of the composition, the total content of component (B) and component (C) in the mixture 1 obtained in step 1 is further preferably 20% by mass or less, further more preferably 10% by mass or less, further more preferably 5.0% by mass or less, further more preferably 2.0% by mass or less, further more preferably 1.0% by mass or less.

[0211] In addition, in the case of a method for producing an aqueous composition or an emulsified composition and having step 4-2, from the viewpoint of improving the stability of the composition, the amount of water used in step 1 is preferably 20% by mass or more, more preferably 25% by mass or more, preferably 90% by mass or less, and more preferably 85% by mass or less, based on 100% by mass of the total amount of the composition finally obtained.

[0212] In the case of a method for producing an emulsified composition and comprising step 4-1, the total content of component (B) and component (C) in the mixture 1 obtained in step 1 is further preferably 0.5% by mass or more, further preferably 1.0% by mass or more, from the viewpoint of improving the texture-enhancing effect on the treated object and the sustainability of the effect, particularly improving the tangling-inhibiting effect on the fibers for hair or hair ornament products when used for treating the fibers for hair or hair ornament products and the sustainability of the effect, and improving moisture resistance. Furthermore, from the viewpoint of improving the stability of the composition, it is further more preferably 80% by mass or less, further more preferably 50% by mass or less, and further more preferably 30% by mass or less.

[0213] Furthermore, in the case of a method for producing an emulsified composition and having step 4-1, from the viewpoint of improving the stability of the composition, the amount of water used in step 1 is preferably 1.0% by mass or more, more preferably 3.0% by mass or more, even more preferably 5.0% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, based on 100% by mass of the total amount of the composition finally obtained.

[0214] In the preparation of mixture 1 in step 1, any components other than (A) cationic polymer and (D) acid may be appropriately formulated. From the viewpoint of improving the stability of the composition, the total content of components (B), (C) and water in mixture 1 is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further more preferably 95% by mass or more, and is 100% by mass or less.

[0215] <Step 2: Preparation of mixture 2>

[0216] In step 2, the mixture 1 is mixed with (D) an acid or an aqueous solution thereof to prepare a mixture 2 comprising (B) anionic polymer, (C) nonionic polymer, (D) acid and water. The preparation conditions (apparatus used, preparation temperature, mixing time) of the mixture 2 in step 2 are the same as those in step 1.

[0217] In the manufacture of an aqueous composition, the component (D) used in step 2 is preferably the total amount of the component (D) used to manufacture the composition; in the manufacture of an emulsified composition, the component (D) used in step 2 does not need to be the total amount of the component (D) used to manufacture the composition, as long as it is at least a portion.

[0218] In step 2, water may be added together with component (D). However, from the viewpoint of improving the stability of the composition, the amount of water used in step 2 is preferably 0.01% by mass or more and preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and further preferably 0.2% by mass or less, based on 100% by mass of the total amount of the composition finally obtained.

[0219] <Step 3: Preparation of aqueous composition (mixture 3)>

[0220] In step 3, the mixture 2 is mixed with the (A) cationic polymer. Through step 3, an aqueous composition (mixture 3) containing the (A) cationic polymer, the (B) anionic polymer, the (C) nonionic polymer, the (D) acid and water is obtained.

[0221] In step 3, the cationic polymer (A) may be directly mixed with the mixture 2. However, from the viewpoint of ease of production, it is preferred to mix the mixture 2 with a solution prepared by dissolving or dispersing the component (A) in water.

[0222] As the solution formed by dissolving or dispersing component (A) in water, a commercially available aqueous solution or aqueous dispersion can also be used. In addition, for example, the reaction solution when using water as the reaction solvent to manufacture component (A) can also be used as the solution formed by dissolving or dispersing component (A) in water.

[0223] The other preparation conditions of the aqueous composition (mixture 3) in step 3 (apparatus used, preparation temperature, mixing time) are the same as those in step 1.

[0224] In step 3, water may be added to adjust the aqueous composition (mixture 3) to a desired concentration.

[0225] In the method for producing an aqueous composition, the amount of water used in step 3 may be an amount such that the total content of components (A) to (C) in the aqueous composition is preferably within the above range.

[0226] In the case of a method for producing an emulsified composition and having step 4-1, from the viewpoint of improving the stability of the composition, the content of water in the mixture 3 obtained through step 3 is preferably 5.0% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, and preferably 50% by mass or less, more preferably 40% by mass or less, based on 100% by mass of the total amount of the composition finally obtained.

[0227] In the method for producing an emulsified composition and having step 4-2, from the viewpoint of improving the stability of the composition, the water content in the mixture 3 obtained through step 3 is preferably 20% by mass or more and 90% by mass or less based on 100% by mass of the total amount of the composition finally obtained.

[0228] <Step 4: Emulsification step>

[0229] In the method for producing an emulsified composition, after step 3, any of the following steps 4-1 and 4-2 is included. This makes it possible to produce an emulsified composition that has high stability, improves the texture-improving effect of the treated object and the sustainability of the effect, and has moisture resistance, and, when used for treating hair or fibers for hair ornaments, can improve the tangling-inhibiting effect of hair or fibers for hair ornaments and the sustainability of the effect, and can inhibit the splitting of the treated hair or fibers for hair ornaments under high humidity conditions.

[0230] Step 4-1: A step of mixing an aqueous phase containing water and an oil phase containing an oily component to prepare an emulsion, and then mixing the emulsion with the mixture 3 described above.

[0231] Step 4-2: A step of mixing the mixture 3 with an aqueous phase containing water and then mixing with an oil phase containing an oil component to emulsify the mixture.

[0232] (Process 4-1)

[0233] In step 4-1, an aqueous phase containing water and an oil phase containing an oily component are mixed to prepare an emulsion, and then the emulsion is mixed with the mixture 3 described above.

[0234] As the "water phase containing water" mentioned here, it is preferred that the balance is water. In addition, the "oil phase containing oily components" preferably contains (E) a cationic surfactant and (F) a higher alcohol as oily components, and the oil phase may further contain (H) an aqueous medium, an alcohol containing an aromatic ring, etc. From the viewpoint of stably forming an emulsion, the total content of the component (E) and the component (F) in the oil phase is preferably 30% by mass or more, more preferably 50% by mass or more, further preferably 70% by mass or more, and is 100% by mass or less.

[0235] The temperature at which the aqueous phase and the oil phase are mixed in step 4-1 is not particularly limited, but is preferably 40° C. or higher, more preferably 45° C. or higher, and even more preferably 50° C. or higher from the viewpoint of producing an emulsified composition having high stability, capable of improving the texture-enhancing effect of the treated object and the sustainability of the effect, and moisture resistance, particularly when used for treating hair or fibers for hair ornaments, capable of improving the tangling-inhibiting effect of hair or fibers for hair ornaments and the sustainability of the effect, and capable of inhibiting the split ends of the treated hair or fibers for hair ornaments under high humidity conditions. From the viewpoint of inhibiting thermal degradation of the formulated components, it is preferably 90° C. or lower, and even more preferably 80° C. or lower. Furthermore, the temperature at which the aqueous phase and the oil phase are mixed in step 4-1 is preferably 40° C. or higher and 90° C. or lower, more preferably 45° C. or higher and 90° C. or lower, and even more preferably 50° C. or higher and 80° C. or lower. The mixing time of the aqueous phase and the oil phase in step 4-1 is not particularly limited, but is preferably 1 minute or longer, more preferably 3 minutes or longer, from the viewpoint of preparing an emulsion, and is preferably 1 hour or shorter from the viewpoint of productivity.

[0236] Next, the obtained emulsion is mixed with the mixture 3 described above.

[0237] The emulsion and the mixture 3 may be mixed at once, or one of them may be added to the other in multiple portions and mixed. In addition, the remaining amount of aqueous components ((D) acid, water, (H) aqueous medium, etc.) other than the mixture 3 and oily components ((G) oil, etc.) other than the components (E) and (F) may be added and mixed as needed while the emulsion and the mixture 3 are mixed, or before or after the mixing.

[0238] The temperature at which the emulsion and the mixture 3 are mixed is not particularly limited, but is preferably 50° C. or lower, more preferably 45° C. or lower, preferably 10° C. or higher, more preferably 20° C. or higher, from the viewpoint of the stability of the emulsified composition obtained. Furthermore, the temperature at which the emulsion and the mixture 3 are mixed is preferably 10° C. or higher and 50° C. or lower, more preferably 20° C. or higher and 45° C. or lower.

[0239] The mixing time of the emulsion and the mixture 3 is not particularly limited, but is preferably 1 minute or longer, more preferably 3 minutes or longer, and preferably 1 hour or shorter from the viewpoint of productivity.

[0240] (Process 4-2)

[0241] In step 4-2, the mixture 3 is mixed with an aqueous phase containing water, and then mixed with an oil phase containing an oil component to be emulsified. The "aqueous phase containing water" and "oil phase containing an oil component" mentioned here are the same as those in step 4-1.

[0242] The temperature at which the mixture 3 and the aqueous phase containing water are mixed with the oil phase in step 4-2 is not particularly limited. However, from the viewpoint of producing an emulsified composition having high stability, capable of improving the texture-improving effect of the treated object and the sustainability of the effect, and moisture resistance, and particularly capable of improving the tangling-inhibiting effect and the sustainability of the effect when used for treating hair or fibers for hair ornaments, and capable of inhibiting the split ends of the treated hair or fibers for hair ornaments under high humidity conditions, the temperature is preferably 40°C or higher, more preferably 45°C or higher, and even more preferably 50°C or higher. From the viewpoint of inhibiting thermal degradation of the formulated components, the temperature is preferably 90°C or lower, and even more preferably 80°C or lower. Furthermore, the temperature at which the mixture 3 and the aqueous phase containing water are mixed with the oil phase in step 4-2 is preferably 40°C or higher and 90°C or lower, more preferably 45°C or higher and 90°C or lower, and even more preferably 50°C or higher and 80°C or lower. There is no particular limitation on the mixing time of the mixture 3 and the aqueous phase containing water and the oil phase in step 4-2. From the viewpoint of preparing an emulsion, it is preferably 1 minute or more, more preferably 3 minutes or more, and from the viewpoint of productivity, it is preferably 1 hour or less.

[0243] Next, the remaining amount of aqueous components ((D) acid, water, (H) aqueous medium, etc.) and oily components other than components (E) and (F) ((G) oil, etc.) may be added and mixed with the obtained emulsion as needed.

[0244] For each mixing step in step 4-1 and step 4-2, the same apparatus as that used in steps 1 to 3 can be used.

[0245] The method for producing an emulsified composition may include steps 1 to 3 and any one of step 4-1 or 4-2. From the viewpoint of production simplicity, the method for producing an emulsified composition preferably includes steps 1 to 3 and step 4-2.

[0246] Regarding the above-mentioned embodiments, the present invention further discloses the following.

[0247] <1>

[0248] A method for producing an aqueous composition, wherein the aqueous composition contains (A) a cationic polymer, (B) an anionic polymer, (C) a nonionic polymer, (D) an acid, and water.

[0249] The above-mentioned manufacturing method comprises the following steps 1 to 3 in sequence.

[0250] Step 1: a step of preparing a mixture 1 comprising (B) an anionic polymer, (C) a nonionic polymer and water,

[0251] Step 2: a step of mixing the mixture 1 with (D) an acid or an aqueous solution thereof to prepare a mixture 2 comprising (B) an anionic polymer, (C) a nonionic polymer, (D) an acid and water,

[0252] Step 3: A step of mixing the mixture 2 and the (A) cationic polymer.

[0253] <2>

[0254] A method for producing an emulsion composition, wherein the emulsion composition contains (A) a cationic polymer, (B) an anionic polymer, (C) a nonionic polymer, (D) an acid, an oily component, and water.

[0255] The above-mentioned production method sequentially comprises the following steps 1 to 3, and any one of the steps 4-1 or 4-2.

[0256] Step 1: a step of preparing a mixture 1 comprising (B) an anionic polymer, (C) a nonionic polymer and water,

[0257] Step 2: a step of mixing the mixture 1 with (D) an acid or an aqueous solution thereof to prepare a mixture 2 comprising (B) an anionic polymer, (C) a nonionic polymer, (D) an acid and water,

[0258] Step 3: a step of mixing the mixture 2 with the (A) cationic polymer to prepare a mixture 3 comprising the (A) cationic polymer, the (B) anionic polymer, the (C) nonionic polymer, the (D) acid and water,

[0259] Step 4-1: A step of mixing an aqueous phase containing water and an oil phase containing an oily component to prepare an emulsion, and then mixing the emulsion with the mixture 3.

[0260] Step 4-2: A step of mixing the mixture 3 with an aqueous phase containing water and then mixing with an oil phase containing an oil component to emulsify the mixture.

[0261] <3>

[0262] The production method as described in <2>, wherein the emulsion composition is preferably an oil-in-water emulsion composition.

[0263] <4>

[0264] The production method as described in any one of <1> to <3>, wherein the viscosity of a 1 mass % aqueous solution of the above-mentioned component (A) at 30°C is preferably 1,000 mPa·s or more, more preferably 1,000 mPa·s or more and 100,000 mPa·s or less, further preferably 1,300 mPa·s or more and 80,000 mPa·s or less, further more preferably 1,500 mPa·s or more and 50,000 mPa·s or less, further more preferably 1,700 mPa·s or more and 30,000 mPa·s or less, and further more preferably 1,800 mPa·s or more and 25,000 mPa·s or less.

[0265] <5>

[0266] The production method as described in any one of <1> to <4>, wherein the cationic charge density of the above-mentioned component (A) is preferably 0.1 mmol / g to 20 mmol / g, more preferably 0.2 mmol / g to 15 mmol / g, 0.2 mmol / g to 12 mmol / g, further more preferably 0.3 mmol / g to 10 mmol / g, further more preferably 0.3 mmol / g to 7.0 mmol / g, further more preferably 0.5 mmol / g to 5.0 mmol / g.

[0267] <6>

[0268] The production method as described in any one of <1> to <5>, wherein the above-mentioned component (A) is one or more selected from the group consisting of cationized polyvinyl alcohol, polyethylene imine, methacryloylethyltrimethylammonium salt polymer, quaternized dialkylaminoalkyl (meth)acrylate polymer, diallyl quaternized ammonium salt polymer, methacrylamidepropyltrimethylammonium salt polymer, vinylimidazolium trichloride-vinyl pyrrolidone copolymer (polyquaternium-16), vinyl pyrrolidone-alkylamino (meth)acrylate copolymer, vinyl pyrrolidone-alkylamino (meth)acrylate-vinyl caprolactam copolymer, alkyl acrylamide-(meth)acrylate-alkylaminoalkyl acrylamide-polyethylene glycol (meth)acrylate copolymer, and adipic acid-dimethylaminohydroxypropylethylenetriamine copolymer.

[0269] <7>

[0270] The production method as described in any one of <1> to <6>, wherein the component (A) is a polymer containing a structural unit represented by the following general formula (1),

[0271]

[0272] In formula (1), R1 is a hydrogen atom or a methyl group, R 2 ~R 4 Each independently represents an alkyl group having 1 to 4 carbon atoms, X represents -O- or -NH-, and m represents a number of 1 to 4.

[0273] <8>

[0274] The production method as described in <7>, wherein the content of the structural unit represented by the general formula (1) in the above-mentioned component (A) is preferably 8.0 mol% or more, more preferably 10 mol% or more and 100 mol% or less in the total structural units constituting the component (A).

[0275] <9>

[0276] The production method as described in any one of <1> to <8>, wherein the component (A) is preferably at least one selected from methacryloylethyltrimethylammonium salt polymers and quaternized dialkylaminoalkyl (meth)acrylate polymers, and more preferably selected from methacryloylethyltrimethylammonium chloride polymers (Polyquaternium-37), methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (Polyquaternium-49), methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (Polyquaternium-50), methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (Polyquaternium-60), methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (Polyquaternium-70), methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (Polyquaternium-80), methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (Polyquaternium-90), methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (Polyquaternium-10 ... Methylammonium chloride-2-hydroxyethyl methacrylate copolymer (Polyquaternium-48), and N,N-dimethylaminoethyl methacrylate diethyl sulfate-N,N-dimethylacrylamide-dimethacrylate polyethylene glycol copolymer (Polyquaternium-52) are preferably one or more, and methacryloylethyltrimethylammonium chloride polymer (Polyquaternium-37) and N,N-dimethylaminoethyl methacrylate diethyl sulfate-N,N-dimethylacrylamide-dimethacrylate polyethylene glycol copolymer (Polyquaternium-52) are more preferably one or more.

[0277] <10>

[0278] The production method according to any one of <1> to <9>, wherein the component (B) comprises (B1) one or more selected from a cross-linked polymer comprising a structural unit derived from (meth)acrylic acid and anionic polysaccharides.

[0279] <11>

[0280] The production method as described in <10>, wherein the cross-linked polymer containing a structural unit derived from (meth)acrylic acid is a homopolymer or copolymer of (meth)acrylic acid having a cross-linked structure, or a salt thereof.

[0281] <12>

[0282] The production method as described in <11>, wherein the homopolymer of (meth)acrylic acid is one or more selected from the group consisting of polyacrylic acid, polymethacrylic acid, and salts thereof.

[0283] <13>

[0284] The production method as described in <11>, wherein the above-mentioned (meth)acrylic acid copolymer is one or more selected from (meth)acrylic acid / maleic acid copolymers, (meth)acrylic acid / itaconic acid copolymers, (meth)acrylic acid / fumaric acid copolymers, (meth)acrylic acid / vinyl acetate copolymers, (meth)acrylic acid / (meth)acrylic acid alkyl ester copolymers, (meth)acrylic acid / 2-hydroxyethyl methacrylate copolymers, acrylic acid / alkyl acrylate / (N-alkyl)acrylamide copolymers, and salts thereof, preferably (meth)acrylic acid / alkyl (meth)acrylate, and more preferably acrylic acid / alkyl acrylate.

[0285] <14>

[0286] The production method as described in any one of <10> to <13>, wherein the cross-linked polymer containing a structural unit derived from (meth)acrylic acid is one or more selected from carboxyvinyl polymer or its salt, (acrylate / alkyl acrylate (C10-30)) cross-linked polymer, (sodium acrylate / acryloyldimethyltaurate / dimethylacrylamide) cross-linked polymer, and acrylate cross-linked polymer-4.

[0287] <15>

[0288] A production method as described in any one of <10> to <14>, wherein the anionic polysaccharide is selected from one or more of polysaccharides having a carboxyl group, sulfates of polysaccharides, and salts thereof, preferably a polysaccharide having a carboxyl group or a salt thereof, more preferably alginic acid, carboxymethyl cellulose or a salt thereof, and further preferably alginic acid or a salt thereof.

[0289] <16>

[0290] A production method as described in any one of <10> to <15>, wherein the above-mentioned component (B1) is preferably one or more selected from carboxyvinyl polymers, (acrylate / alkyl acrylate (C10-30)) cross-linked polymers, and anionic polysaccharides, more preferably anionic polysaccharides or salts thereof, and further preferably alginic acid or salts thereof.

[0291] <17>

[0292] The production method as described in any one of <10> to <16>, wherein the anion charge density of the above-mentioned component (B1) is preferably from 1.0 mmol / g to 25 mmol / g, more preferably from 2.0 mmol / g to 20 mmol / g, and further preferably from 3.5 mmol / g to 15 mmol / g.

[0293] <18>

[0294] The production method as described in any one of <10> to <17>, wherein the weight average molecular weight (Mw) of the anionic polysaccharide as the above-mentioned component (B1) is preferably 2,000 to 3.5 million, more preferably 10,000 to 3 million, further preferably more than 30,000 and 3 million, and further more preferably 50,000 to 3 million.

[0295] <19>

[0296] A production method as described in any one of <10> to <18>, wherein the content of the above-mentioned component (B1) in the above-mentioned component (B) is preferably 50 mass% or more, more preferably 60 mass% or more, further preferably 70 mass% or more, further more preferably 80 mass% or more, and is 100 mass% or less.

[0297] <20>

[0298] The production method according to any one of <10> to <19>, wherein the component (B) further comprises (B2) an anionic polymer other than the component (B1).

[0299] <21>

[0300] The production method as described in <20>, wherein the molecular weight of the above-mentioned component (B2) is preferably 1,000 to 50,000, more preferably 1,000 to 30,000, further preferably 2,000 to 30,000, further more preferably 5,000 to 30,000, further more preferably 10,000 to 30,000.

[0301] <22>

[0302] The production method as described in <20> or <21>, wherein the component (B2) is preferably a polymer having a carboxyl group and having a molecular weight of 1,000 to 50,000, more preferably 1,000 to 30,000, and more preferably a non-crosslinked polymer having a molecular weight of 1,000 to 30,000 containing a structural unit derived from (meth)acrylic acid.

[0303] <23>

[0304] The production method as described in <22>, wherein the non-crosslinked polymer containing a structural unit derived from (meth)acrylic acid is one or more selected from poly(meth)acrylic acid, (meth)acrylic acid / maleic acid copolymer, (meth)acrylic acid / itaconic acid copolymer, (meth)acrylic acid / fumaric acid copolymer, (meth)acrylic acid / vinyl acetate copolymer, (meth)acrylic acid / (meth)acrylic acid alkyl ester copolymer, (meth)acrylic acid / 2-hydroxyethyl methacrylate copolymer, acrylic acid / alkyl acrylate / (N-alkyl)acrylamide copolymer, and salts thereof.

[0305] <24>

[0306] The production method according to any one of <20> to <23>, wherein the component (B2) is at least one selected from poly(meth)acrylic acid, (meth)acrylic acid / alkyl (meth)acrylate copolymers, and salts thereof.

[0307] <25>

[0308] A production method as described in any one of <20> to <24>, wherein the anion charge density of the above-mentioned component (B2) is preferably from 1.0 mmol / g to 25 mmol / g, more preferably from 3.0 mmol / g to 20 mmol / g, and further preferably from 5.0 mmol / g to 15 mmol / g.

[0309] <26>

[0310] A manufacturing method as described in any one of <20> to <25>, wherein the content of the above-mentioned component (B2) in the above-mentioned component (B) is preferably from 1 mass % to 50 mass %, more preferably from 2 mass % to 40 mass %, further preferably from 3 mass % to 30 mass %, and further more preferably from 5 mass % to 20 mass %.

[0311] <27>

[0312] A manufacturing method as described in any one of <20> to <26>, wherein the mass ratio of the above-mentioned component (B2) to the total amount of the above-mentioned component (B1) and the above-mentioned component (B2) [(B2) / {(B1)+(B2)}] is preferably from 0.01 to 1.0, more preferably from 0.02 to 0.80, further preferably from 0.05 to 0.50, and further more preferably from 0.08 to 0.30.

[0313] <28>

[0314] A production method as described in any one of <1> to <27>, wherein the above-mentioned component (C) is one or more selected from polyalkylene glycol or its derivatives, polymers containing structural units derived from vinyl pyrrolidone, polymers containing structural units derived from (meth)acrylates, polyvinyl alcohol, polyacrylamide, and polycaprolactam.

[0315] <29>

[0316] The production method as described in <28>, wherein the polyalkylene glycol is preferably at least one selected from polyethylene glycol, polypropylene glycol, and a polyethylene glycol-polypropylene glycol copolymer, and more preferably at least one selected from polyethylene glycol and a polyethylene glycol-polypropylene glycol copolymer.

[0317] <30>

[0318] A production method as described in <28>, wherein the above-mentioned polyalkylene glycol derivative is one or more selected from polyalkylene glycol monoalkyl ether, polyalkylene glycol dialkyl ether, polyalkylene glycol monoaryl ether, polyalkylene glycol diaryl ether, polyalkylene glycol monofatty acid ester, polyalkylene glycol difatty acid ester, and polyalkylene glycol diglycidyl ether, preferably one or more selected from polyalkylene glycol monoalkyl ether, polyalkylene glycol dialkyl ether, polyalkylene glycol monofatty acid ester, and polyalkylene glycol difatty acid ester, and more preferably one or more selected from polyalkylene glycol monofatty acid ester and polyalkylene glycol difatty acid ester.

[0319] <31>

[0320] A manufacturing method as described in any one of <1> to <30>, wherein the above-mentioned component (C) is preferably one or more selected from polyalkylene glycol or its derivatives, and a polymer containing a structural unit derived from vinyl pyrrolidone, more preferably one or more selected from polyethylene glycol, polypropylene glycol, polyethylene glycol-polypropylene glycol copolymer, these mono- or di-fatty acid esters, and polyvinyl pyrrolidone, and further preferably one or more selected from polyethylene glycol, polyethylene glycol-polypropylene glycol copolymer, these mono- or di-fatty acid esters, and polyvinyl pyrrolidone.

[0321] <32>

[0322] The production method as described in any one of <1> to <31>, wherein the weight average molecular weight of the component (C) is preferably 2,000 to 2,000,000, more preferably 5,000 to 1,500,000, and even more preferably 8,000 to 1,50,000.

[0323] <33>

[0324] The production method as described in any one of <1> to <32>, wherein the component (D) is preferably an organic acid, and more preferably at least one selected from carboxylic acid compounds and sulfonic acid compounds other than the component (B).

[0325] <34>

[0326] A production method as described in <33>, wherein the above-mentioned organic acid is preferably one or more selected from aliphatic dicarboxylic acids, hydroxycarboxylic acids, and aromatic sulfonic acids, more preferably one or more selected from succinic acid, lactic acid, malic acid, glycolic acid, p-toluenesulfonic acid, and naphthalenesulfonic acid, further preferably one or more selected from succinic acid and lactic acid, and further more preferably lactic acid.

[0327] <35>

[0328] The production method according to any one of <2> to <34>, wherein the emulsified composition contains an oily component, preferably an oily component comprising (E) a cationic surfactant and (F) a higher alcohol.

[0329] <36>

[0330] The production method as described in <35>, wherein the above-mentioned component (E) is preferably one or more selected from the group consisting of (i) alkyltrimethylammonium salts, (ii) alkoxyalkyltrimethylammonium salts, (iii) dialkyldimethylammonium salts, (iv) alkylamidealkyltrimethylammonium salts, (v) alkyldimethylamines and salts thereof, (vi) alkoxyalkyldimethylamines and salts thereof, and (vii) alkylamidealkyldimethylamines and salts thereof, and more preferably selected from the group consisting of (i) alkyltrimethylammonium salts and (vi) alkoxyalkyldimethylamines and salts thereof The present invention further preferably comprises at least one selected from cetyl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, behenyl trimethyl ammonium chloride, N,N-dimethyl-3-hexadecyloxypropylamine or its lactate, and N,N-dimethyl-3-octadecyloxypropylamine (stearyloxypropyl dimethylamine) or its lactate, and further preferably comprises at least one selected from behenyl trimethyl ammonium chloride and N,N-dimethyl-3-octadecyloxypropylamine (stearyloxypropyl dimethylamine) or its lactate.

[0331] <37>

[0332] A manufacturing method as described in <35> or <36>, wherein the above-mentioned component (F) is one or more selected from lauryl alcohol, cetyl alcohol, myristyl alcohol, oleyl alcohol, stearyl alcohol, isostearyl alcohol, 2-octyldodecanol, behenyl alcohol, and cetearyl alcohol, and preferably one or more selected from cetyl alcohol, myristyl alcohol, stearyl alcohol, and behenyl alcohol.

[0333] <38>

[0334] The production method according to any one of <2> to <37>, wherein the emulsified composition further contains (G) an oil agent.

[0335] <39>

[0336] A manufacturing method as described in <38>, wherein the above-mentioned component (G) is one or more selected from (a) silicone oil, (b) ester oil, (c) ether oil, (d) hydrocarbon oil, (e) higher fatty acid, and (f) waxes, preferably one or more selected from (a) silicone oil, (b) ester oil, (d) hydrocarbon oil, and (e) higher fatty acid, and more preferably (a) silicone oil.

[0337] <40>

[0338] The production method according to any one of <2> to <39>, wherein the emulsified composition further contains (H) an aqueous medium.

[0339] <41>

[0340] The production method as described in <40>, wherein the component (H) is one or more selected from ethanol, isopropanol, 1,3-butylene glycol, glycerol, ethylene glycol, propylene glycol, and dipropylene glycol.

[0341] <42>

[0342] A production method as described in any one of <1> to <41>, wherein the content of the above-mentioned component (A) in the above-mentioned aqueous composition and emulsified composition is preferably 0.01 mass% to 3.0 mass%, more preferably 0.02 mass% to 2.5 mass%, further preferably 0.05 mass% to 2.0 mass%, further more preferably 0.1 mass% to 1.5 mass%, further more preferably 0.1 mass% to 1.0 mass%.

[0343] <43>

[0344] The production method as described in any one of <1> to <42>, wherein the content of the above-mentioned component (B) in the above-mentioned aqueous composition and emulsified composition is preferably 0.005 mass% to 3.0 mass%, more preferably 0.01 mass% to 2.0 mass%, further preferably 0.02 mass% to 1.5 mass%, further more preferably 0.02 mass% to 1.0 mass%, further more preferably 0.02 mass% to 0.5 mass%, further more preferably 0.02 mass% to 0.3 mass%, further more preferably 0.02 mass% to 0.3 mass%, further more preferably 0.02 mass% to 0.2 mass%, further more preferably 0.02 mass% to 0.1 mass%, further more preferably 0.02 mass% to 0.1 mass%.

[0345] <44>

[0346] A production method as described in any one of <1> to <43>, wherein the total content of the above-mentioned component (A) and the above-mentioned component (B) in the above-mentioned aqueous composition and emulsified composition is preferably 0.02 mass% to 5.0 mass%, more preferably 0.04 mass% to 4.0 mass%, further preferably 0.05 mass% to 3.0 mass%, and even more preferably 0.1 mass% to 2.0 mass%.

[0347] <45>

[0348] The production method as described in any one of <1> to <44>, wherein the mass ratio of the above-mentioned component (A) to the above-mentioned component (B) in the above-mentioned aqueous composition and emulsified composition [(A) / (B)] is preferably 1.0 to 30, more preferably 1.0 to 20, further preferably 2.0 to 20, further preferably 3.0 to 20, further more preferably 4.5 to 20, further more preferably 4.7 to 18, further more preferably 4.8 to 18, further more preferably 5.0 to 18, further more preferably 5.5 to 16, further more preferably 6.0 to 16, further more preferably 6.2 to 15, further more preferably 6.5 to 15, further more preferably 6.5 to 12, further more preferably 6.5 to 10.

[0349] <46>

[0350] A production method as described in any one of <1> to <45>, wherein the content of the above-mentioned component (C) in the above-mentioned aqueous composition and emulsified composition is preferably from 0.02 mass% to 5.0 mass%, more preferably from 0.04 mass% to 4.0 mass%, further preferably from 0.05 mass% to 3.0 mass%, and even more preferably from 0.1 mass% to 2.0 mass%.

[0351] <47>

[0352] A production method as described in any one of <1> to <46>, wherein the mass ratio of the above-mentioned component (C) to the total amount of the above-mentioned component (A) and the above-mentioned component (B) in the above-mentioned aqueous composition and emulsified composition [(C) / {(A)+(B)}] is preferably 0.2 to 20, more preferably 0.3 to 15, further preferably 0.4 to 10, further preferably 0.5 to 8.0, further more preferably 0.6 to 5.0, further more preferably 0.8 to 2.0, further more preferably 0.8 to 1.5.

[0353] <48>

[0354] The production method as described in any one of <1> to <47>, wherein the content of the component (D) in the aqueous composition and the emulsified composition is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and preferably 3.0% by mass or less.

[0355] <49>

[0356] The production method as described in any one of <1> to <48>, wherein the content of water in the above-mentioned aqueous composition and emulsified composition is preferably 50 mass% or more, more preferably 70 mass% or more, further preferably 80 mass% or more, and further more preferably 85 mass% or more.

[0357] <50>

[0358] A production method as described in any one of <35> to <49>, wherein the content of the above-mentioned component (E) in the above-mentioned emulsion composition is preferably from 0.1 mass % to 10 mass %, more preferably from 0.2 mass % to 5.0 mass %, further preferably from 0.5 mass % to 5.0 mass %, and further more preferably from 1.0 mass % to 3.5 mass %.

[0359] <51>

[0360] The production method as described in any one of <35> to <50>, wherein the content of the above-mentioned component (F) in the above-mentioned emulsion composition is preferably from 0.1 mass % to 15 mass %, more preferably from 0.2 mass % to 12 mass %, further preferably from 0.5 mass % to 12 mass %, and further more preferably from 1.0 mass % to 10 mass %.

[0361] <52>

[0362] A production method as described in any one of <38> to <51>, wherein the content of the above-mentioned component (G) in the above-mentioned emulsion composition is preferably from 0.1 mass % to 20 mass %, more preferably from 0.2 mass % to 10 mass %, further preferably from 0.5 mass % to 10 mass %, and further more preferably from 0.5 mass % to 5.0 mass %.

[0363] <53>

[0364] A production method as described in any one of <40> to <52>, wherein the content of the above-mentioned component (H) in the above-mentioned aqueous composition and emulsified composition is preferably from 0.1 mass % to 10 mass %, more preferably from 0.2 mass % to 5.0 mass %, and further preferably from 0.5 mass % to 5.0 mass %.

[0365] <54>

[0366] A production method as described in any one of <1> to <53>, wherein the pH value of the aqueous solution obtained by diluting the above-mentioned aqueous composition and emulsified composition with water by 20 times at 25°C is preferably 3.0 or more, more preferably 3.2 or more, preferably 7.5 or less, more preferably 7.0 or less, further preferably 6.0 or less, and further more preferably 5.0 or less.

[0367] <55>

[0368] A production method as described in any one of <1> to <54>, wherein in the above-mentioned step 1, the temperature when preparing the above-mentioned mixture 1 is preferably from 40°C to 90°C, more preferably from 45°C to 80°C, further preferably from 50°C to 70°C, and further more preferably from 50°C to 65°C.

[0369] <56>

[0370] A manufacturing method as described in any one of <1> to <55>, wherein the total content of the above-mentioned component (B) and the above-mentioned component (C) in the above-mentioned mixture 1 is preferably 0.03 mass% or more, more preferably 0.1 mass% or more, further preferably 0.3 mass% or more, and is preferably 50 mass% or less, more preferably 40 mass% or less, and further preferably 35 mass% or less.

[0371] <57>

[0372] A manufacturing method as described in <56>, wherein, when the above-mentioned manufacturing method is a method having the above-mentioned step 4-2, the total content of the above-mentioned component (B) and the above-mentioned component (C) in the mixture 1 obtained in the above-mentioned step 1 is further preferably 20 mass% or less, further more preferably 10 mass% or less, further more preferably 5 mass% or less, further more preferably 2.0 mass% or less, further more preferably 1.0 mass% or less.

[0373] <58>

[0374] A manufacturing method as described in any one of <1> to <57>, wherein, when the above-mentioned manufacturing method is a method having the above-mentioned step 4-2, the amount of water used in the above-mentioned step 1 is preferably 20 mass% or more, more preferably 25 mass% or more, preferably 90 mass% or less, more preferably 85 mass% or less, based on 100 mass% of the total amount of the above-mentioned composition finally obtained.

[0375] <59>

[0376] A production method as described in <56>, wherein, when the above-mentioned production method is a production method for the above-mentioned emulsified composition and has the method of the above-mentioned step 4-1, the total content of the above-mentioned component (B) and the above-mentioned component (C) in the mixture 1 obtained in the above-mentioned step 1 is further preferably 0.5% by mass or more, further more preferably 1.0% by mass or more, and further more preferably 80% by mass or less, further more preferably 50% by mass or less, further more preferably 30% by mass or less.

[0377] <60>

[0378] A production method as described in any one of <2> to <59>, wherein, when the above-mentioned production method is a production method for the above-mentioned emulsified composition and is a method having the above-mentioned step 4-1, the amount of water used in the above-mentioned step 1 is preferably 1.0 mass% or more, more preferably 3.0 mass% or more, and further preferably 5.0 mass% or more, based on the amount of 100 mass% of the total amount of the composition finally obtained, and is preferably 50 mass% or less, more preferably 40 mass% or less, and further preferably 30 mass% or less.

[0379] <61>

[0380] A production method as described in any one of <2> to <60>, wherein, when the above-mentioned production method is the production method of the above-mentioned emulsified composition and is a method having the above-mentioned step 4-1, the content of water in the mixture 3 obtained through the above-mentioned step 3 is preferably 5.0 mass% or more, more preferably 10 mass% or more, further preferably 15 mass% or more, preferably 50 mass% or less, more preferably 40 mass% or less, based on the total amount 100 mass% of the composition finally obtained.

[0381] <62>

[0382] The production method according to any one of <2> to <61>, wherein the production method of the emulsified composition comprises steps 1 to 3 and step 4-2.

[0383] [Example]

[0384] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to the scope of the examples. In addition, each measurement and evaluation in the examples were performed by the following methods.

[0385] (Measurement of Viscosity of 1 Mass % Aqueous Solution of Cationic Polymer)

[0386] A 1 mass % aqueous solution of the cationic polymer used in each example was prepared, and the viscosity of the aqueous solution at 30° C. was measured using a B-type viscometer (TV-20 manufactured by Toki Sangyo).

[0387] (Determination of pH value)

[0388] The conditioner of each example was diluted 20 times with water, and the pH value at 25° C. was measured using a pH meter (F-51 manufactured by Horiba, Ltd.).

[0389] (The look and feel of conditioner)

[0390] 1 g of the conditioner of each example was dropped onto a black plastic plate 2 days after preparation, and the appearance when it was passed 10 times with fingers and the touch when crushed with fingers were evaluated according to the following criteria.

[0391] A: No aggregated particles are visible and it feels smooth when crushed with fingers.

[0392] B: Although no aggregated particles can be seen, it feels rough when crushed with fingers.

[0393] C: Aggregated particles are visible and feel rough when crushed with fingers.

[0394] D: Separation.

[0395] (Treatment with conditioner + measurement of combing force after 2 shampooings)

[0396] (1) 7 mL of "Kao Bubble Hair Bleach L" (first dose) and 15 mL of "Kao Bubble Hair Dye D" (second dose) manufactured by Kao Corporation were mixed and applied to a Japanese hair tress having a length of 20 cm and a mass of 30 g. After standing for 20 minutes, the tress was thoroughly rinsed with warm water at 35 to 40°C (bleaching treatment). This bleaching treatment was repeated 4 times to prepare a damaged hair tress for evaluation. The hair tress was washed with a normal shampoo of the following composition and made to contain 15 g ± 0.5 g of water.

[0397] (2) Apply 1.5 mL of the conditioner of each example to the above-mentioned hydrated hair bundle, apply it by hand and leave it for 30 seconds, then rinse it with warm water at 35-40°C for 15 seconds. Then, rub the front and back of the hair bundle 20 times each within 30 seconds with 1 mL of the above-mentioned ordinary shampoo, and rinse it for 15 seconds.

[0398] (3) Apply 1 mL of a normal hair conditioner with the following composition, rub it with your hands for 30 seconds, and rinse for 15 seconds. Then, use 1 mL of the normal shampoo to rub the front and back of the hair bundle 20 times each within 30 seconds, and rinse for 15 seconds.

[0399] (4) After combing with a brush to completely untangle the knot, the water content of the rinsed hair bundle was adjusted to 15 g ± 0.5 g, and the hair bundle was set in a combing force measuring device (KOT-0303 manufactured by Utsunomiya Seiki Co., Ltd.), and two brushes (Kao Lunette) were passed through the uppermost part of the hair bundle, and the hair bundle was combed at a fixed speed (60 rpm) to measure the load (g) applied when the comb passed through the hair tip. The hair bundle was combed 50 times, and the average value of the combing load at a total of 50 points was defined as the value of "combing force immediately after treatment". The smaller the combing force value, the better the result. The combing load of the damaged hair bundle (water content 15 g ± 0.5 g) that was not subjected to the treatment of (2) above was 2055 g, and the combing force was judged to be good when it was 1900 g or less.

[0400] [Composition of regular shampoo] *The amount of preparation is the amount of active ingredients.

[0401]

[0402] (*1) 42.0% by mass based on EMAL E-27C (active ingredient content 27% by mass) manufactured by Kao Corporation

[0403] (*2) AMINON C-11S (manufactured by Kao Corporation), active ingredient content 100% by mass

[0404] [Composition of regular conditioner] *The amount of the formulated ingredient is the amount of the active ingredient.

[0405]

[0406] (*3) FARMIN DM-E80 manufactured by Kao Corporation, active ingredient content 90% by mass

[0407] (*4) KALCOL 8098 manufactured by Kao Corporation, active ingredient content 100% by mass

[0408] (*5) PURAC ULTRAPURE90 manufactured by PURAC Thailand Ltd., active ingredient content 90% by mass

[0409] (Wetness resistance of treated hair)

[0410] 7 mL of "Kao Foam Hair Bleach L" (first dose) and 15 mL of "Kao Foam Hair Dye D" (second dose) manufactured by Kao Corporation were mixed and applied to a Japanese hair tress with a length of 30 cm and a mass of 20 g. After standing for 20 minutes, the tress was thoroughly rinsed with warm water at 35 to 40°C (bleaching treatment). This bleaching treatment was repeated 4 times to prepare a damaged hair tress for evaluation.

[0411] After washing the hair bundle with the above-mentioned ordinary shampoo, 1 mL of the conditioner of each example was applied for 30 seconds and left in this state for 1 minute, then rinsed with running water at 35 to 40° C. for 30 seconds and dried with a hair dryer until completely dry.

[0412] The dried hair was straightened 10 times using a hair straightener (AHI-938 manufactured by Miki Electric Industry Co., Ltd.) set at 160°C while being combed, and a photo of the hair immediately after being straightened was taken. Next, the straightened hair was hung and left to stand for 30 minutes in a high humidity environment of 35°C and 80%RH, and a photo was taken again. In both photos, the hair width at a position 23.5 cm from the root of the hair was measured, and the change in the hair width immediately after straightening and after being stored under high humidity was calculated according to the following formula.

[0413] Hair strand width change value = (hair strand width after storage at high humidity) / (hair strand width immediately after straightening)

[0414] When the value is 1.3 or more, the appearance also looks broad, so it is judged that the moisture resistance is low.

[0415] Examples 1 to 11 (Production of Hair Conditioner (Aqueous Composition))

[0416] Using the respective components in the amounts described in Table 1, a hair conditioner (aqueous composition) was prepared in the following procedure.

[0417] <Process 1>

[0418] Anionic polymer (component (B1), or component (B1) and component (B2)) pre-dispersed in dipropylene glycol and dipropylene glycol (component (H)) were added to a 500 mL beaker containing water, and heated and stirred at 56° C. using a stirring device (mechanical stirrer equipped with two stirring blades). After confirming that the anionic polymer was completely dissolved, (C) nonionic polymer was further added and completely dissolved to obtain mixture 1.

[0419] <Process 2>

[0420] A mixture 2 is obtained by adding (D) acid to the mixture 1 and stirring the mixture.

[0421] <Process 3>

[0422] The cationic polymer (A) dispersed in water in advance was added to the mixture 2. The mixture was heated and stirred at 56°C to completely dissolve the cationic polymer, thereby obtaining a hair conditioner.

[0423] The obtained conditioner was used to perform evaluation according to the above method. The results are shown in Table 1.

[0424] Comparative Example 1

[0425] In step 1, the same operations as in Examples 1 to 11 were carried out to obtain a mixture 1.

[0426] The (A) cationic polymer dispersed in water in advance was added to the mixture 1. After heating and stirring at 56°C to completely dissolve the cationic polymer, the (D) acid was added and stirred to obtain a hair conditioner.

[0427] The obtained conditioner was used to perform evaluation according to the above method. The results are shown in Table 2.

[0428] Comparative Example 2

[0429] The acid (D) was added to a 500 mL beaker containing water. Then, the anionic polymer (component (B1) and component (B2)) pre-dispersed in dipropylene glycol was added, and heated and stirred at 56° C. using a stirring device. After confirming that the anionic polymer was completely dissolved, the nonionic polymer (C) was further added and completely dissolved to obtain a mixture.

[0430] The (A) cationic polymer dispersed in water in advance was added to the mixture, and the mixture was heated and stirred at 56° C. to completely dissolve the cationic polymer, thereby obtaining a hair conditioner.

[0431] The obtained conditioner was used to perform evaluation according to the above method. The results are shown in Table 2.

[0432] Comparative Example 3

[0433] The (D) acid was added to a 500 mL beaker containing water. Then, the (A) cationic polymer dispersed in water was added. The mixture was heated and stirred at 56° C. using a stirring device to completely dissolve the cationic polymer, thereby obtaining a mixture.

[0434] To this mixture, (B) anionic polymer (component (B1) and component (B2)) dispersed in dipropylene glycol in advance was added, and heated and stirred at 56° C. using a stirrer. After confirming that the anionic polymer was completely dissolved, (C) nonionic polymer was further added and completely dissolved to obtain a hair conditioner.

[0435] The obtained conditioner was used to perform evaluation according to the above method. The results are shown in Table 2.

[0436] Comparative Example 4

[0437] The cationic polymer (A) was added to a 500 mL beaker filled with water, and heated and stirred at 56° C. using a stirring device to completely dissolve the cationic polymer.

[0438] Next, anionic polymers (components (B1) and (B2)) dispersed in dipropylene glycol in advance were added and heated and stirred at 56° C. After confirming that the anionic polymers were completely dissolved, (C) nonionic polymers were further added and completely dissolved to obtain a mixture.

[0439] (D) Acid is added to the mixture and stirred to obtain a hair conditioner.

[0440] The obtained conditioner was used to perform evaluation according to the above method. The results are shown in Table 2.

[0441] Comparative Example 5

[0442] The cationic polymer (A) was added to a 500 mL beaker filled with water, and the mixture was heated and stirred at 56° C. using a stirring device to completely dissolve the cationic polymer.

[0443] After adding (D) the acid and stirring, the anionic polymer (component (B1) and component (B2)) dispersed in dipropylene glycol in advance was added, and heated and stirred at 56° C. After confirming that the anionic polymer was completely dissolved, the nonionic polymer (C) was further added and completely dissolved to obtain a hair conditioner.

[0444] The obtained conditioner was used to perform evaluation according to the above method. The results are shown in Table 2.

[0445] Example 12 (Production of Hair Conditioner (Emulsified Composition))

[0446] Using the respective components in the amounts described in Table 3, a hair conditioner (emulsified composition) was prepared in the following procedure.

[0447] <Process 1>

[0448] An anionic polymer (component (B1), or component (B1) and component (B2)) pre-dispersed in dipropylene glycol (100% by mass of the total amount) was added to a 500 mL beaker filled with water, and heated and stirred at 56° C. using a stirring device (mechanical stirrer equipped with two stirring blades). After confirming that the anionic polymer was completely dissolved, (C) a nonionic polymer was further added and completely dissolved to obtain a mixture 1.

[0449] <Process 2>

[0450] A mixture 2 is obtained by adding (D) acid to the mixture 1 and stirring the mixture.

[0451] <Process 3>

[0452] The cationic polymer (A) dispersed in water in advance was added to the mixture 2. The mixture was heated and stirred at 56°C to completely dissolve the cationic polymer, thereby obtaining an aqueous composition (mixture 3).

[0453] <Process 4-2>

[0454] The remaining amount of water heated to 56°C was added to the mixture 3. Then, an oil phase obtained by mixing (E) a cationic surfactant, (F) a higher alcohol, the remaining dipropylene glycol, and benzyl alcohol in advance and dissolving them at 85°C was added, and stirred at 56°C for 10 minutes. After stirring for 10 minutes, the heating was terminated and air cooling was started. The remaining amount of (D) an acid (90% lactic acid) and polydimethylsiloxane were added thereto, and the mixture was cooled while stirring until the liquid temperature reached 40°C or less to obtain a hair conditioner.

[0455] The obtained conditioner was used to perform evaluation according to the above method. The results are shown in Table 3.

[0456] Embodiments 13 to 16

[0457] <Steps 1 to 3>

[0458] About steps 1 to 3, the same operation as in Example 12 was carried out to obtain an aqueous composition (mixture 3). However, the amount of water used in step 1 was set as the amount described in Table 3.

[0459] <Process 4-1>

[0460] The remaining amount of water heated to 56°C, (E) cationic surfactant, (F) higher alcohol, remaining dipropylene glycol, and benzyl alcohol were mixed in advance and dissolved at 85°C to the aqueous composition (mixture 3) obtained in step 3. The oil phase was added and stirred at 56°C for 10 minutes (preparation of emulsion). After stirring for 10 minutes, heating was terminated and air cooling was started. Mixture 3 obtained in step 3, (D) the remaining amount of acid (90% lactic acid), and polydimethylsiloxane were added thereto, and the mixture was cooled while stirring until the liquid temperature reached 40°C or less to obtain a conditioner.

[0461] The obtained conditioner was used to perform evaluation according to the above method. The results are shown in Table 3.

[0462]

[0463]

[0464]

[0465]

[0466] The components described in Tables 1 and 2 are as follows: The blending amounts (mass %) described in the tables are effective amounts of the respective components.

[0467] *1: Sodium alginate, Kimika Argin I-3-15 manufactured by Kimika Corporation.

[0468] *2: Carboxyvinyl polymer, Carbopol 980 manufactured by Lubrizol Advanced Materials, Inc.

[0469] *3: (Acrylates / Alkyl Acrylate (C10-30)) Crosspolymer, Pemulen TR-1 manufactured by Lubrizol Advanced Materials, Inc.

[0470] *4: (Acrylic acid / stearyl acrylate) copolymer, Sofcare SA-37W manufactured by Kao Corporation, Mw: 20,000.

[0471] *5: Polyacrylic acid, JURYMER AC-10L manufactured by Toagosei Co., Ltd., Mw: 20,000-30,000.

[0472] *6: Polyethylene glycol, Blaunon PEG-20000S manufactured by Aoki Oil & Fats Industries, Ltd., Mw: 20,000.

[0473] *7: Polyvinyl pyrrolidone, Luviskol K90 manufactured by BASF Japan Co., Ltd., Mw: 1.2 million.

[0474] *8: Polyoxyethylene polyoxypropylene glycol (150 E.O.) (35 P.O.), Pronon #208 manufactured by NOF Corporation, Mw: 9,000.

[0475] *9: Polyoxyethylene polyoxypropylene glycol (240 E.O.) (60 P.O.), Unilube 75DE-2620R manufactured by NOF Corporation, Mw: 14,000.

[0476] *10: Dipropylene glycol, DPG-RF manufactured by ADEKA Corporation.

[0477] *11: 90% lactic acid, PURAC ULTRAPURE90 manufactured by PURAC Thailand Ltd.

[0478] *12: Polyquaternium-52 (N,N-dimethylaminoethyl methacrylate diethylsulfate-N,N-dimethylacrylamide-dimethacrylate polyethylene glycol copolymer), Sofcare KG-101W-E manufactured by Kao Corporation.

[0479] *13: Polyquaternium-52 (N,N-dimethylaminoethyl methacrylate diethyl sulfate-N,N-dimethylacrylamide-dimethacrylate polyethylene glycol copolymer), Sofcare KG-301W manufactured by Kao Corporation.

[0480] *14: Polyquaternium-37 (methacryloylethyltrimethylammonium chloride polymer), Cosmedia Ultragel 300 manufactured by BASF JAPAN Co., Ltd., content of the structural unit represented by the general formula (1): 100 mol%.

[0481]

[0482]

[0483] The components described in Table 3 are as follows. In addition, the blending amount (mass %) described in the table is an effective amount of each component.

[0484] *1: Sodium alginate, Kimika Argin I-3-15 manufactured by Kimika Co., Ltd.

[0485] *2: (Acrylic acid / stearyl acrylate) copolymer, Sofcare SA-37W manufactured by Kao Corporation.

[0486] *3: Polyethylene glycol, Blaunon PEG-20000S manufactured by Aoki Oil & Fats Industries, Ltd., Mw: 20,000.

[0487] *4: Dipropylene glycol, DPG-RF manufactured by ADEKA Corporation.

[0488] *5: 90% lactic acid, PURAC ULTRAPURE90 manufactured by PURAC Thailand Ltd.

[0489] *6: Polyquaternium-52 (N,N-dimethylaminoethyl methacrylate diethylsulfate-N,N-dimethylacrylamide-dimethacrylate polyethylene glycol copolymer), Sofcare KG-101W-E manufactured by Kao Corporation.

[0490] *7: Behenyltrimethylammonium chloride, Quartamin 2285-E manufactured by Kao Corporation.

[0491] *8: Cetyl alcohol, Kalcol 6870 manufactured by Kao Corporation.

[0492] *9: Amino-modified silicone-polydimethylsiloxane mixture, DOWSIL CF1046 manufactured by Dow Toray Co., Ltd.

[0493] As shown in Tables 1 to 3, it can be seen that the conditioners of the aqueous compositions or emulsified compositions obtained by the manufacturing method of the present invention have high stability, and when used for hair treatment, can improve the anti-tangling effect of hair and its sustainability, and can inhibit the split ends of the treated hair under high humidity conditions.

[0494] In addition, from the comparison of Examples 12 to 16 in Table 3, it can be seen that in the production of the emulsified composition, when the amount of water used in step 1 is 5% by mass or more (Examples 13 to 16), the stability of the obtained emulsified composition is further improved.

[0495] [Industrial Applicability]

[0496] According to the present invention, there is provided a method for producing an aqueous composition and an emulsified composition, wherein the aqueous composition and the emulsified composition contain a polyion complex and have high stability, and can improve the texture improvement effect of the treated object and the sustainability of the effect, as well as moisture resistance. In particular, when used for treating hair or fibers for headdress products, the aqueous composition and the emulsified composition can improve the tangle suppression effect of hair or fibers for headdress products and the sustainability of the tangle suppression effect, and can suppress the split ends of the treated hair or fibers for headdress products under high humidity conditions.

Claims

1. A method for producing an aqueous composition, wherein: The aqueous composition contains (A) a cationic polymer, (B) an anionic polymer, (C) a nonionic polymer, (D) an acid, and water. The manufacturing method comprises the following steps 1 to 3 in sequence: Step 1: a step of preparing a mixture 1 comprising (B) an anionic polymer, (C) a nonionic polymer and water; Step 2: a step of mixing the mixture 1 with (D) an acid or an aqueous solution thereof to prepare a mixture 2 comprising (B) an anionic polymer, (C) a nonionic polymer, (D) an acid and water; Step 3: A step of mixing the mixture 2 and the (A) cationic polymer.

2. A method for producing an emulsified composition, wherein: The emulsified composition contains (A) a cationic polymer, (B) an anionic polymer, (C) a nonionic polymer, (D) an acid, an oily component, and water. The manufacturing method comprises the following steps 1 to 3, and any one of steps 4-1 or 4-2 in sequence. Step 1: a step of preparing a mixture 1 comprising (B) an anionic polymer, (C) a nonionic polymer and water; Step 2: a step of mixing the mixture 1 with (D) an acid or an aqueous solution thereof to prepare a mixture 2 comprising (B) an anionic polymer, (C) a nonionic polymer, (D) an acid and water; Step 3: a step of mixing the mixture 2 with (A) a cationic polymer to prepare a mixture 3 comprising (A) a cationic polymer, (B) an anionic polymer, (C) a nonionic polymer, (D) an acid and water; Step 4-1: a step of mixing an aqueous phase containing water and an oil phase containing an oily component to prepare an emulsion, and then mixing the emulsion with the mixture 3; Step 4-2: A step of mixing the mixture 3 with an aqueous phase containing water and then mixing with an oil phase containing an oily component to emulsify the mixture.

3. The manufacturing method according to claim 2, wherein: The oily component includes (E) a cationic surfactant and (F) a higher alcohol.

4. The production method according to any one of claims 1 to 3, wherein The component (B) includes a component (B1) of at least one selected from a cross-linked polymer including a structural unit derived from (meth)acrylic acid and an anionic polysaccharide.

5. The manufacturing method according to claim 4, wherein: The component (B) further includes a component (B2) an anionic polymer other than the component (B1).

6. The production method according to any one of claims 1 to 5, wherein The mass ratio (A) / (B) of the component (A) to the component (B) contained in the composition is 1.0 to 30.

7. The manufacturing method according to claim 5 or 6, wherein: The mass ratio (B2) / {(B1)+(B2)} of the component (B2) to the total amount of the component (B1) and the component (B2) is 0.01 or more and 1.0 or less.

8. The production method according to any one of claims 1 to 7, wherein The total content of the component (A) and the component (B) contained in the composition is 0.02 mass % or more and 5.0 mass % or less.

9. The production method according to any one of claims 1 to 8, wherein The mass ratio (C) / {(A)+(B)} of the component (C) contained in the composition to the total amount of the component (A) and the component (B) is 0.2 or more and 20 or less.

Citation Information

Patent Citations

  • Keratin treating composition

    JP1978139734A

  • Production of hair treating agent composition

    JP1999116445A

  • Cosmetic compositions and cleaning care products

    JP2020536857A

  • Composition containing polyion complex and texture agent

    JP2021031468A